Method for recovering raw materials from polyurethane materials
Recycling the polyol and amine in polyurethane materials through alcoholization and hydrolysis reactions, combined with the steps of separation, distillation and adsorption to solve the problem of low quality recovery in existing technology, and achieve efficient and high -quality recovery effects.
Patent Information
- Application Number
- CN202380046395.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to effectively recover polyols and amine substances in polyurethane materials, and the recycling quality is not high, which affects the subsequent phosgeneization process.
The polyurethane material is contacted with alcoholized substances and water, and alcoholization and hydrolysis reactions are performed to form a mixture rich in polyol and amine, and the raw materials are purified by steps separation, distillation and adsorption.
The efficient recovery of polyol and amine substances in polyurethane materials, optimization of recycling quality obtained is suitable for subsequent optomization processes.
Smart Images

Figure BDA0005182049790000561 
Figure BDA0005182049790000571 
Figure HDA0005182049830000011
Abstract
Description
[0001] The present invention relates to a method for recovering raw materials from polyurethane materials. Exemplary raw materials are polyol substances and / or amine substances.
[0002] Furthermore, the present invention relates to a method for preparing a polyurethane material by reacting a polyol substance obtained by the method of the present invention with an isocyanate substance.
[0003] Furthermore, the present invention relates to a process for producing an isocyanate substance, preferably a toluene diisocyanate (TDI) substance, from an amine substance, preferably a toluene diamine (TDA)-based substance, obtained by the process according to the invention.
[0004] Products containing polyurethane materials are widely used in industry and everyday applications. Due to the enormous and still increasing popularity of polyurethane materials, there is a large amount of polyurethane material waste (for example, waste from old mattresses or furniture or car seats). This polyurethane material waste should be used appropriately and as ecologically friendly as possible.
[0005] One way of such use of the polyurethane material is to recover raw materials from the polyurethane material.
[0006] Besides so-called mechanical recycling methods which involve physical comminution, chemical recycling methods are also known.
[0007] A method for recovering raw materials from polyurethane products is known from WO 2020 / 260387 A1, which comprises the following steps: (A) providing a polyurethane product based on an isocyanate component and a polyol component; (B) reacting the polyurethane product with a (mono- or polyhydric) alcohol in the presence of a catalyst to obtain a first product mixture; (C) obtaining the polyols from the first product mixture, comprising: (CI) mixing the first product mixture obtained in step (B) with an organic solvent that is not completely miscible with the alcohol used in step (B), without previously removing any water that may be contained in the first product mixture, and carrying out phase separation to form a first alcohol phase and a first solvent phase; (C.II) processing the first solvent phase and obtaining polyols; and preferably (D) obtaining amines.
[0008] WO 2021 / 023889 A1 discloses a method for the alcoholization and hydrolysis of a polyurethane material made from at least one polyol compound and at least one toluene diisocyanate-based compound, wherein the method comprises the following steps: contacting the polyurethane material with at least one alcoholizing compound to form a reaction mixture (M0), and allowing the polyurethane material and the alcoholizing compound to react in the reaction mixture (M0) to form a mixture (M); allowing the mixture (M) to separate into at least an upper phase and a lower phase, wherein phase (A) and phase (B) are two immiscible phases; subjecting phase (B) to at least one hydrolysis step to form phase (B1); wherein the at least one alcoholizing compound is characterized in that it has a melting point below 200°C; wherein the at least one alcoholizing compound is characterized in that it has a hydroxyl functionality of at least 2; and the condition is that the at least one alcoholizing compound is not glycerol.
[0009] However, there is a need for a method of recovering raw materials with optimized purity from polyurethane materials.
[0010] With regard to polyols recovered from polyurethane materials, the following points must be considered:
[0011] - Amine species, such as toluenediamine, are often carcinogenic and therefore need to be separated from the corresponding recovered polyol species;
[0012] - Potassium ions as well as acids need to be removed because they make the corresponding recovered polyol material less suitable for foaming applications.
[0013] For the recovery of amine species from polyurethane materials, a process must be developed that minimizes the capture of the corresponding amine species in the carbamate. Furthermore, to obtain amines suitable for subsequent phosgenation, the amine species must be substantially free of solids, basic or acidic impurities, and polyol residues. Among other process and product quality drawbacks, residual polyols react with isocyanates during or after phosgenation, leading to a decrease in the NCO content and potentially solids formation, with an increased risk of equipment fouling.
[0014] In view of the above, an object of the present invention is to provide a method for recovering raw materials from polyurethane materials which is as simple as possible and allows recovery of raw materials of optimized quality.
[0015] This object is achieved by providing a method according to claim 1 .
[0016] Typically, polyurethane materials comprise or consist of a structure that is formed by a polyaddition reaction of a (poly)isocyanate (=isocyanate species of the polyurethane material) and a polyol (=polyol species of the polyurethane material). For example, a structure based on a diisocyanate O=C=NRN=C=O and a diol HO-R'-OH (wherein R and R' represent organic groups) can be depicted as
[0017] -[O-R'-O-(O=C)-HN-R-NH-(C=O)]-
[0018] Many polyurethane materials, such as elastic and / or flexible polyurethane foams, contain significant amounts of urethane and urea linkages.
[0019] The method of the present invention preferably includes an alcoholization step, preferably combined with a hydrolysis step, in which the polyurethane material is contacted with an alcoholizing substance. During the alcoholization of the polyurethane material, a mixture containing a polyol substance and an amine substance is formed. According to a preferred aspect of the present invention, the polyurethane material is contacted with the alcoholizing substance and water. Hydrolysis of the polyurethane material occurs due to the addition of water or due to the presence of water in the original polyurethane material. Advantageously, any carbamate formed by transesterification is hydrolyzed to form amines and polyols. The presence of at least an equimolar amount of water can result in approximately 100% release of the amines.
[0020] Particularly for recovering amine species, it is beneficial if the polyurethane material is alcoholized by contacting the polyurethane material with an alcoholizing species, wherein water is added in an amount such that the resulting mixture has a water content of from about 0.2 eq. to about 30 eq. of water, preferably from about 20 eq. of water, particularly from about 1 eq. to about 10 eq. of water, and especially from about 1.15 eq. to about 6 eq. of water, for example from about 1.3 eq. to about 4 eq. of water, for example from about 1.4 eq. to about 2 eq. of water, based on the amount of cleavable bonds in the polyurethane material. During alcoholization (i.e., alcoholysis) of the polyurethane material, amine species and polyol species are formed.
[0021] Eq. (i.e., equivalent weight) refers to the equivalent weight of each breakable bond of the polyurethane material. Breakable bonds are defined as urethane bonds and urea bonds within the polyurethane material and include segments in the polyurethane material where the segments are connected by allophanate units and linkages via biuret groups.
[0022] Basically, the amount of scissile bonds is equal to the amount of isocyanate groups in the original polyurethane material.
[0023] In the case where the polyurethane material already contains water, it may not be necessary to add water in order to adjust the water content of the mixture to about 0.2 eq. to about 30 eq. of water, preferably to about 20 eq. of water, particularly about 1 eq. to about 10 eq., especially about 1.15 eq. to about 6 eq., for example about 1.3 eq. to about 4 eq., for example about 1.4 eq. to about 2 eq. of water, based on the amount of breakable bonds in the polyurethane material.
[0024] In the event that the original water content of the polyurethane material is not within the stated range, about 0.2 eq. to about 30 eq. of water, preferably about 20 eq. of water, particularly about 1 eq. to about 10 eq., especially about 1.15 eq. to about 6 eq., for example about 1.3 eq. to about 4 eq., for example about 1.4 eq. to about 2 eq. of water may be added based on the amount of breakable bonds in the polyurethane material.
[0025] The water content of the mixture can also be adjusted to about 0.2 wt.-% to about 35 wt.-%, preferably about 0.2 wt.-% to about 10 wt.-%, in particular about 2 wt.-% to about 8 wt.-%, for example about 2.5 wt.-% to about 7 wt.-%, based on the total weight of the mixture.
[0026] Preferably, the process comprises allowing the mixture to settle, wherein a phase rich in polyol species, in particular a first phase, and a phase rich in alcoholized species, in particular a second phase, are formed.
[0027] Furthermore, in particular for recovering polyol substances, the method preferably comprises post-processing the polyol-rich phase, in particular the first phase, by purifying the polyol substances. The purification comprises two or more of the following:
[0028] - evaporating the phase in one or more evaporators, in particular in a second distillation;
[0029] - contacting the phase with an ion exchange material;
[0030] - bringing this phase into contact with one or more adsorbents.
[0031] After the post-treatment, the phase rich in polyol substances, in particular the first phase, preferably has an acid value of 0.1 mg KOH / g or less.
[0032] The acid number (corresponding to the acid value) was determined according to DIN EN ISO 4629-2 (with minor modifications). A 1:1 mixture of isopropanol / water was used as the solvent mixture instead of toluene / ethanol 2:1. As a further modification, the NaOH / KOH was dissolved in methanol instead of ethanol.
[0033] Particularly for recovering the amine species, the method further comprises post-processing the mixture by purifying the amine species, comprising the following:
[0034] In the first distillation, the phase rich in alcoholic substances, in particular the second phase, is distilled in order to purify the amine substances.
[0035] The first distillation typically comprises one or more distillation stages. Preferably, the first distillation comprises at least two distillation stages. Preferred embodiments of the first distillation will be described in more detail below.
[0036] Preferably, the mixture is post-treated so that the alcoholated species are partially or substantially completely released and / or recovered.
[0037] Good results have been obtained for examples of the method in which the amine substance comprises or consists of a substance based on toluene diamine (TDA).
[0038] Among the alternatives to TDA-based amine species, it is possible that the amine species comprises or consists of diamines or polyamines of the diphenylmethane (MDA) series or other amines, the corresponding isocyanates of which are typically used to produce polyurethane materials.
[0039] In the context of the present invention, the term polyol substance encompasses all polyols known to those skilled in the art in connection with polyurethane chemistry, such as, in particular, polyether polyols, polyester polyols, polyether ester polyols and polyether carbonate polyols. The term "a polyol substance" typically encompasses embodiments in which two or more different polyols have been used to prepare the polyurethane material. This also applies to the polyol class.
[0040] The polyol-rich phase and the alcoholized phase may be the same. In these embodiments, the mixture is a one-phase system and / or a monophasic system.
[0041] In other particularly preferred embodiments of the method, the mixture is a multiphase system, preferably a biphasic system. In embodiments in which the mixture is a biphasic system, the first phase is rich in polyol material and the second phase is rich in alcoholic material.
[0042] In a multiphase system, such as a biphasic system, the different phases are immiscible at 25° C. For example, the first phase and the second phase are immiscible at 25° C.
[0043] "Rich in polyol species" preferably means that the respective phase contains at least about 46 wt.-%, preferably about 70 wt.-% or more polyol species, based on the total weight of the phase, in particular before post-treatment.
[0044] "Rich in alcoholic substances" preferably means that the respective phase contains at least about 65 wt.-%, preferably about 70 wt.-% or more alcoholic substances, based on the total weight of the phase, in particular before work-up.
[0045] The first phase preferably has a lower density than the second phase.
[0046] The polyurethane material is preferably a polyurethane foam, a polyurethane elastomer, a polyurethane adhesive, a polyurethane coating or a mixture thereof.
[0047] Particularly in embodiments where the amine species is recovered, it may be beneficial to remove excess water from the mixture, preferably by evaporating the excess water, before allowing the mixture to settle. In particular, the mixture may be heated and / or vacuum applied to evaporate the excess water. For example, the excess water may be removed by flash evaporation or by applying a vacuum to the heated mixture.
[0048] For example, the water removal step is performed for about 120 minutes or less, in particular about 90 minutes or less, such as about 75 minutes or less, for example about 60 minutes or less.
[0049] Preferably, the water removal step is performed for about 10 minutes or longer, in particular about 30 minutes or longer, such as about 40 minutes or longer.
[0050] In embodiments where flash evaporation is used to remove water, the removal step (ie, flash evaporation) is performed for 15 minutes or less.
[0051] According to one aspect of the invention, solids are removed from the mixture before or after allowing the mixture to settle, preferably by one or more of the following: filtration, centrifugation, decantation. The mentioned techniques are part of or constitute solid-liquid separation.
[0052] For example, after alcoholysis or after excess water has been removed, the mixture is filtered, particularly at a temperature of about 70°C to about 200°C.
[0053] For filtration, a filter membrane with an average pore size of about 30 μm or less is preferably used. The use of a cascade filter may be advantageous. For example, the first filter membrane of the cascade filter has an average pore size of about 250 μm to about 290 μm. The second filter membrane of the cascade filter preferably has an average pore size of about 50 μm to about 90 μm, and in particular, the third filter membrane of the cascade filter has an average pore size of 20 μm or less.
[0054] In the alternative or in addition, centrifugation is a preferred solid-liquid separation method.For example, the mixture is centrifuged after alcoholysis or after excess water has been removed.
[0055] Preferably, the mixture is centrifuged at a temperature of 70° C. or higher, particularly about 90° C. or higher and / or about 160° C. or lower, particularly about 140° C. or lower. For example, the mixture is centrifuged at about 2500 rpm to about 14000 rpm, preferably about 3000 rpm to about 6000 rpm.
[0056] Performing a solid-liquid separation before phase separation generally results in improved phase separation. During solid-liquid separation, solids that slow down or deteriorate phase separation are removed. For example, the formation of mulm between the two phases can be avoided or reduced. This mulm stabilizes the mixture and deteriorates phase separation.
[0057] It is also possible to carry out more than one solid-liquid separation step.
[0058] For example, the following solid-liquid separation methods can be combined:
[0059] - decantation and filtration; or
[0060] - Centrifugation and filtration.
[0061] It is possible to carry out the solid-liquid separation steps sequentially. Alternatively, one solid-liquid separation step may be carried out before the mixture is allowed to settle, and another solid-liquid separation step may be carried out at the start of the work-up of the phase rich in polyol material, in particular the first phase, or the phase rich in alcoholized material, in particular the second phase.
[0062] According to one aspect of the present invention, it may be beneficial if one or more adsorbents are added prior to removing the solids. For example, the one or more adsorbents may act as a filter aid.
[0063] According to one aspect of the invention, the mixture is contacted with one or more adsorbents before being allowed to settle, wherein preferably the one or more adsorbents are selected from the group consisting of activated carbon, silicon dioxide, silicates, in particular alkali metal silicates and / or alkaline earth metal silicates (e.g. magnesium silicate), or mixtures of two or more thereof. Particularly preferred is the use of silicates, such as magnesium silicate and / or sodium silicate, as adsorbents before phase separation.
[0064] According to one aspect of the present invention, the phase rich in polyol material, in particular the first phase, is purified by performing a solid-liquid separation (in which solids are removed) before purification, wherein the solid-liquid separation comprises or consists of one or more of the following: filtration, centrifugation, decantation.
[0065] According to a preferred embodiment, the phase rich in polyol substances, in particular the first phase, is filtered before purification.
[0066] In particular, the phase rich in polyol material, in particular the first phase, is filtered through a filter membrane having an average mesh size of about 20 μm or less.
[0067] Filtration is preferably performed by using cascade filters.
[0068] For example, the first filter membrane of the cascade filter has an average mesh size of about 250 μm to about 290 μm. The second filter membrane of the cascade filter preferably has an average mesh size of about 50 μm to about 90 μm, and in particular, the third filter membrane of the cascade filter has an average mesh size of 20 μm or less.
[0069] According to one example, the polyol-rich phase, in particular the first phase, is allowed to settle, and the released supernatant is separated from the solid by pumping and / or decanting the supernatant, and then the supernatant is further processed into the polyol-rich phase, in particular the first phase.
[0070] In an alternative or in addition, centrifugation is a preferred solid-liquid separation method.For example, the phase rich in polyol species, in particular the first phase, is centrifuged before further purification.
[0071] Preferably, the phase rich in polyol substances, in particular the first phase, is centrifuged at a temperature of 70° C. or higher, in particular about 90° C. or higher and / or about 160° C. or lower, in particular about 140° C. or lower. For example, the phase rich in polyol substances, in particular the first phase, is centrifuged at about 2,500 rpm to about 14,000 rpm, preferably about 3,000 rpm to about 6,000 rpm.
[0072] For example, in embodiments where solid-liquid separation is not performed before or shortly after allowing the mixture to settle, it may be beneficial to remove solids from the alcoholate-rich phase, particularly the second phase. Preferred solid-liquid separation methods are: filtration, centrifugation, decantation, or a combination of two or more thereof.
[0073] For optimized yield of release of starting material, the alcoholization step is preferably carried out in the presence of a catalyst, wherein preferably the catalyst is selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carboxylates (especially acetates), alkaline earth metal carboxylates (especially acetates), Lewis acids (especially dibutyltin dilaurate), organic amines (especially imidazole or diethanolamine), organometallic compounds (especially rare earth metal catalysts, for example titanium tert-butoxide), or tin compounds (such as tin octoate).
[0074] As the alkali metal hydroxide, it is particularly preferable to use potassium hydroxide (KOH), sodium hydroxide (NaOH) or cesium hydroxide (CsOH).
[0075] According to a particularly preferred embodiment, potassium hydroxide is used as a catalyst for the alcoholation reaction.
[0076] According to another particularly preferred embodiment, sodium hydroxide is used as catalyst.
[0077] According to a preferred embodiment, the catalyst (e.g. potassium hydroxide or sodium hydroxide) is used in an amount of about 0.2 wt.-% or more and / or about 35 wt.-% or less, preferably about 5 wt.-% or less, in particular about 0.4 wt.-% or more and / or about 3.5 wt.-% or less, for example about 1 wt.-% or more and / or about 2 wt.-% or less, based on the total weight of the mixture.
[0078] Preferably, the catalyst (e.g. KOH or NaOH) is used in an amount of about 0.2 wt.-% or more and / or about 35 wt.-% or less, preferably about 6.5 wt.-% or less, in particular about 0.8 wt.-% or more and / or about 5 wt.-% or less, for example about 1 wt.-% or more and / or about 4 wt.-% or less, based on the total weight of the polyurethane material. In particular, the catalyst is used in an amount of about 1.5 wt.-% or more and / or about 3.5 wt.-% or less, based on the total weight of the polyurethane material.
[0079] During the step of allowing the mixture to settle, phase separation of the mixture into the first phase and the second phase preferably occurs during and / or after settling.
[0080] In particular, after the workup, at the end of the process, the first phase has a potassium content of about 0.1 wt.-% or less, preferably about 0.01 wt.-% or less, for example about 0.005 wt.-% or less, based on the total weight of the phase. The above threshold values are also valid for embodiments of the process in which potassium hydroxide is used as catalyst in the alcoholization step.
[0081] Preferably, the potassium content is about 0.004 wt.-% or less, based on the total weight of the first phase.
[0082] To determine the potassium content, an automated wet chemical digestion was performed, followed by determination of the potassium content by ICP / OES (Inductively Coupled Plasma / Optical Emission Spectroscopy).
[0083] As alcoholizing substances, alcohols are preferably used.
[0084] For example, the alcoholized substance includes or consists of one or more of methanol, ethanol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, methylene glycol, triethylene glycol, glycerol, 2-methyl-1,3-propanediol, and mixtures of two or more thereof.
[0085] The inventors have observed that in the examples where dipropylene glycol was used as alcoholising substance, a single-phase mixture was produced (after settling).
[0086] For the alcoholized polyurethane material, it is preferred to use about 0.2 parts by weight or more and / or about 5 parts by weight or less of the alcoholized substance per part by weight of the polyurethane material. Preferably, about 0.4 parts by weight or more and / or about 2 parts by weight or less of the alcoholized substance per part by weight of the polyurethane material is used, particularly about 0.6 parts by weight or more and / or about 1.5 parts by weight or less of the alcoholized substance per part by weight of the polyurethane material, for example about 0.8 parts by weight or more and / or about 1.2 parts by weight or less of the alcoholized substance per part by weight of the polyurethane material is used.
[0087] According to a preferred embodiment, a phase separation is performed after the mixture has settled, wherein a phase rich in polyol substances, in particular the first phase, is separated from a phase rich in alcoholized substances, in particular the second phase.
[0088] Preferably, the phase separation is carried out in a phase separation apparatus. To improve the phase separation, it may be beneficial to remove the water contained in the mixture, for example, by flash evaporation. Water removal can also be accomplished by applying a vacuum to the mixture or simply distilling the mixture at atmospheric pressure. In principle, the phase separation can also be improved by adding salt or by using specific internals in the phase separation apparatus.
[0089] Alternatively, the phase separation is promoted by adding a halogenated or non-halogenated hydrocarbon, or a mixture of several halogenated or non-halogenated hydrocarbons, which are immiscible or only partially miscible with the alcoholating substance.
[0090] According to another aspect, phase separation is promoted by the addition of a glycol (eg, diethylene glycol).
[0091] To further improve the purity of the polyol species, it is beneficial if the post-treatment further includes a final distillation of the polyol species-rich phase, in particular a final distillation of the first phase, as the last step. As an alternative to the final distillation, it may be beneficial to apply a vacuum while stirring and heating the polyol species-rich phase (e.g., 100° C. to 150° C.).
[0092] The distillation as the last step of the post-treatment is hereinafter particularly referred to as the third distillation. Preferably, the third distillation is performed by using one or more evaporators.
[0093] According to a preferred embodiment, the one or more evaporators for post-processing the polyol-rich phase, in particular the first phase, are selected from one or more of the following: thin film evaporator, short path evaporator, falling film evaporator, rotary evaporator.
[0094] The post-processing of the phase rich in polyols, in particular the post-processing of the first phase, comprises a first part in which one or more evaporators are used and a second part in which one or more adsorbents are used. However, as mentioned above, it may also be beneficial to use one or more adsorbents before the one or more evaporators.
[0095] It is advantageous if the post-treatment of the polyol-rich phase, in particular the first phase, comprises combining evaporation of the polyol-rich phase, in particular the first phase, in a thin film evaporator with subsequent evaporation of the polyol-rich phase, in particular the first phase, in a short path evaporator.
[0096] The post-treatment of the polyol-rich phase, in particular the first phase, preferably comprises contacting the polyol-rich phase, in particular the first phase, with a cation exchange material or an anion exchange material or contacting the phase with a cation exchange material and an anion exchange material sequentially or simultaneously.
[0097] For example, ion exchange materials are used, ie cation exchange materials, anion exchange materials or a mixture of both.
[0098] An anion exchange material may be used in the first ion exchange step and a cationic material may be used in the second ion exchange step, or vice versa. In the alternative, an anion exchange material and a cation exchange material may be used simultaneously.
[0099] As cation exchange materials, either strongly acidic materials or weakly acidic materials can be used. The material can be a polymer resin comprising or consisting of cross-linked polystyrene, polyacrylate or polymethacrylate polymers containing carboxylic acid or sulfonic acid groups. Strongly acidic materials containing sulfonic acid groups are preferred. Materials of this type include those available from LANXESS Germany GmbH. K 2431, K 2621 and K 2629, from DuPont TM )of 15. 35 and 40 and C150SH and C160SH from Purolite GmbH, Germany.
[0100] In another embodiment, a weakly acidic material containing a carboxylic acid group is used. Materials of this type include those from DuPont TM )of MAC-3H or from LANXESS Germany GmbH CNP 80.
[0101] As anion exchange material, a weakly basic material or a strongly basic material is used. The material can be a polymer resin consisting of cross-linked polystyrene, polyacrylate or polymethacrylate polymers containing tertiary amino groups and / or quaternary amino groups. Strongly basic materials containing quaternary amino groups are preferred. Examples of such materials are the quaternary amino groups from DuPont. TM )of HPR 9000OH or available from LANXESS Germany GmbH S 6368A. In another embodiment, a weakly basic material containing a tertiary amino group is used. Examples of such materials are LANXESS Germany GmbH MP 62 or from DuPont TM )of A22.
[0102] According to a preferred embodiment, the post-treatment of the phase rich in polyol substances, in particular the first phase, comprises two steps of evaporating the phase rich in polyol substances, in particular the first phase, in a thin film evaporator.
[0103] Preferably, the post-treatment of the phase rich in polyol material, in particular the first phase, comprises contacting the phase rich in polyol material, in particular the first phase, with one or more adsorbents, preferably activated carbon, silica, silicates, in particular alkali metal silicates and / or alkaline earth metal silicates (e.g. magnesium silicate), or a mixture of two or more thereof.
[0104] The adsorbent may be a neutral polymer adsorbent or activated carbon. The preferred adsorbent is activated carbon. The activated carbon may be in powder form or granular form. The preferred activated carbon to be used as the adsorbent is chemically activated carbon. Chemically activated carbon may be derived from plant material and activated with phosphoric acid. This type of activated carbon is available as C GRAN or CNSP 1240 from Norit Activated Carbon or as CERN from Calgon Carbon GmbH, Germany. BGE or BGX. Other types of activated carbon may also be used.
[0105] It may be beneficial if about 2 wt.-% to about 10 wt.-%, preferably about 3 wt.-% to about 8 wt.-%, of the one or more adsorbents, based on the total weight of the phase rich in polyol material, in particular the mixture of the first phase and the one or more adsorbents, are brought into contact with this phase.
[0106] In embodiments where a silicate (eg, magnesium silicate) is used as an adsorbent prior to phase separation, it is typically sufficient if the polyol species-rich phase, particularly the first phase, is purified using ion exchange materials and / or activated carbon.
[0107] In particular, particulate material is used as the adsorbent. For example, particulate material having an average particle size of about 15 μm or more, in particular about 25 μm or more, for example about 35 μm or more is used as the adsorbent.
[0108] Preferably, particulate material is used having an average particle size of about 2 mm or less.
[0109] For example, particulate material having an average particle size of about 85 μm or less, in particular about 75 μm or less, for example about 65 μm or less, is used as the adsorbent.
[0110] Preferred silicates to be used as adsorbents are magnesium silicate or sodium silicate or mixtures thereof.
[0111] Preferably, the one or more adsorbents are used in an amount of about 0.2 wt.-% to about 20 wt.-%, such as about 0.3 wt.-% to about 5 wt.-%, based on the total weight of the first phase.
[0112] In particular, a particulate adsorbent is used. According to one embodiment, a mixture of activated carbon and magnesium silicate powder is used.
[0113] As adsorbents, preferably amorphous materials having a porous internal structure and / or an increased active surface compared to non-porous materials are used. Thus, impurities can be adsorbed on the surface of the adsorbent and removed from the polyol-rich phase, in particular the first phase.
[0114] As already mentioned, alkali metal silicates or alkaline earth metal silicates or mixtures thereof can be used. For example, magnesium silicate can be used as an adsorbent. Magnesium silicate is particularly suitable for removing potassium ions, which are usually used as a catalyst during alcoholization.
[0115] In place of or in addition to magnesium silicate, sodium silicate is considered a suitable adsorbent.
[0116] According to a preferred embodiment, after the post-treatment of the first phase, the first phase ultimately has an aromatic amine content of about 0.03 wt.-% or less, preferably about 0.01 wt.-% or less, for example about 0.005 wt.-% or less, based on the total weight of the first phase. "After post-treatment of the first phase" refers to the state after this process has been carried out and when the first phase is ready for further use (for example, as a polyol for polyurethane production).
[0117] This aromatic amine content refers in particular to embodiments in which the mixture is biphasic and separates into a first phase rich in polyol species and a second phase rich in alcoholated species.
[0118] The amount of aromatic amines is determined by liquid chromatography. For example, 0.01 g of the sample to be analyzed (or 0.5 g if very low amounts of aromatic amines are present in the sample) is diluted to 20 ml of acetonitrile and filtered through a filter with a 0.2 μm mesh size. The resulting mixture is then injected into a reverse phase (RP) high pressure liquid chromatograph (HPLC) with ultraviolet (UV) detection. The amine content is determined in two consecutive runs and quantified using a 5-point calibration with an external standard.
[0119] With the drastic reduction of the amount of aromatic amines, such as toluenediamine (TDA), the resulting polyol substances are particularly suitable as reagents for new polyurethane materials. In particular, due to the carcinogenic properties of TDA, the amount of TDA in the polyol-rich phase should be as small as possible.
[0120] The inventors have found that it is advantageous if the alcoholization step is carried out at an internal temperature of about 120° C. or higher, more preferably about 150° C. or higher, in particular about 160° C. or higher, for example about 170° C. or higher. The internal temperature during alcoholysis is preferably set to about 270° C. or lower, more preferably about 250° C. or lower, in particular about 220° C. or lower, for example about 200° C. or lower. The internal temperature refers to the temperature of the mixture.
[0121] In embodiments where additional water is added, the water may be added prior to heating the mixture, while heating the mixture, or after the mixture has reached the desired temperature.
[0122] In embodiments where water is added, the internal temperature of the mixture is preferably maintained at about 150°C to about 240°C, particularly about 170°C to about 220°C, and at a pressure of about 1 bar to about 60 bar during and after the addition of water.
[0123] Water can be added in a constant process during the alcoholization step. In a preferred embodiment, water is added in a manner such that the internal temperature of the mixture remains constant. In particular, water is added in a manner such that the internal temperature remains at about 150° C. or higher, more preferably 170° C. or higher.
[0124] According to a preferred embodiment, the alcoholization step is carried out under an inert gas atmosphere, for example, under a nitrogen atmosphere. This can reduce discoloration effects. In an alternative embodiment, the alcoholization step is carried out under air. Optionally, a reflux condenser can be used.
[0125] It may be beneficial if the mixture is degassed using standard techniques before carrying out the alcoholysis.
[0126] The reaction time under reflux and / or the reaction time of the alcoholization reaction is preferably set to about 10 minutes or longer, particularly about 20 minutes or longer, for example about 30 minutes or longer, for example about 40 minutes or longer.
[0127] Preferably, the reaction time under reflux and / or the reaction time of the alcoholization reaction is preferably set to about 200 minutes or less, particularly about 175 minutes or less, such as about 150 minutes or less, for example about 135 minutes or less.
[0128] As mentioned, for some embodiments it may be beneficial if the alcoholization is carried out at a pressure of up to about 60 bar, for example in a pressure reactor.
[0129] In embodiments in which one or more evaporators are used during the workup of the polyol-rich phase, in particular the first phase, it is beneficial if one or more of these evaporators is a thin film evaporator or short path evaporator operated at about 180° C. to about 270° C. and / or at a pressure of about 0.1 mbar to about 30 mbar.
[0130] The use of a thin film evaporator facilitates mass transfer processes in the substance to be purified (eg, a polyol substance).
[0131] After post-treatment of the polyol species-rich phase, in particular after post-treatment of the first phase, the phase preferably has a polyol species content of 97 wt.-% or more, in particular 99 wt.-% or more, based on the total weight of the phase.
[0132] The amount of polyol substance is determined by GPC (gel permeation chromatography). As eluent, tetrahydrofuran (THF) is used. THF with toluene as solvent is used as internal standard. As column material, styrene-divinylbenzene (SDV) with a pore size of 1000 angstroms and a particle size of 5 μm is used. A 5 cm pre-column and two 30 cm columns are used. A refractive index (RI) detector and / or a UV / Vis detector are used. Calibration is performed with polyethylene glycol (PEG) obtained from PSS Polymer Standards Service GmbH, 55120 Mainz, Germany. Then, PEG is used as an external standard from BASF Polyurethanes GmbH, 49448 Lemford, Germany. Germany) The polyol content was determined by a 5-point calibration based on the corresponding area integral compared to 2074 (a trifunctional polyether polyol and containing mainly secondary hydroxyl groups).
[0133] By the method of the present invention, about 95% or more, preferably about 97% or more of the polyol substances that can be recovered from the polyurethane material in theory can be released. Therefore, the release yield of the polyol substances is about 95% or more, preferably about 97% or more.
[0134] "Liberation of the polyol species" describes in particular the release of the polyol from all urethane bonds present in the original polyurethane material (free-up and / or liberation).
[0135] According to the present invention, the release yield of the polyol substance is determined by dividing the amount of the polyol substance in the two layers quantified after the alcoholization step by the amount of the polyol substance theoretically obtainable from the polyurethane material.
[0136] According to typical ranges for polyurethane slabstock foam formulations, the theoretically available amount of polyol species is from about 50 wt.-% to about 70 wt.-% of the total weight of the polyurethane material.
[0137] As previously mentioned, according to the present invention, it is preferred that the method be used to treat polyurethane materials having a certain water content. Preferred ranges for the water content have been described above. As also mentioned above, the water content may be initially present in the polyurethane material (either inherently or due to an adsorption process) or additional water may be added.
[0138] In the event that additional water is added, it is preferably added before and / or during the alcoholisation reaction occurs. Preferably, no further water is added after the alcoholisation step.
[0139] In particular, to obtain a biphasic mixture, the settling step is performed by adjusting the temperature of the mixture to room temperature (25°C) to about 160°C, preferably about 80°C to about 120°C, and by keeping the mixture at this temperature until phase separation occurs.
[0140] With respect to embodiments in which water is present during the alcoholization step, the yield of released amine species after the alcoholization step is about 70% or greater, particularly about 85% or greater.
[0141] "Liberation of amine species" describes in particular the release (free-up and / or liberation) of amines from all urethane and urea bonds present in the original polyurethane material.
[0142] The release yield of the amine species is defined as the sum of the free aromatic amine species in the two layers quantified after the alcoholization step divided by the amount of aromatic amine species theoretically available from the polyurethane material.
[0143] Based on the typical range of polyurethane slabstock foam formulations used for the experiments, the theoretically available amount of amine species is from about 20 wt.-% to about 50 wt.-% of the total weight of the polyurethane material.
[0144] According to the invention, the yield of "recovery"—as opposed to "liberation"—of amine species is determined by dividing the amount of amine species quantified after workup by the amount of amine species theoretically obtainable from the polyurethane material.
[0145] Preferably, the phase rich in polyols, in particular the first phase, is distilled in a second distillation to obtain a second distillate. The second distillate and / or each distillate obtained before the first distillation is preferably combined with the phase rich in alcoholic substances, in particular the second phase, before the first distillation.
[0146] Preferably, each distillate containing alcoholated material is combined with the second phase prior to the first distillation.
[0147] For the second distillation, preferably one or more evaporators are used, for example one or more of the following: thin film evaporator, short path evaporator, falling film evaporator, rotary evaporator. In this respect, reference is made to the above and below description of the one or more evaporators.
[0148] Due to the combination of the second distillate with the phase rich in alcoholic substances, the second distillate can be distilled together with the phase rich in alcoholic substances, in particular together with the second phase, in the first distillation.
[0149] In embodiments where the mixture is a single-phase system, preferably a second distillation is performed before the first distillation, wherein both distillations are performed with the same phase (ie, the mixture).
[0150] Preferably, no separate hydrolysis of the alcoholysate-rich phase, in particular the second phase, is performed. In particular, no separate hydrolysis is performed after the alcoholysis of the polyurethane material is complete.
[0151] The first distillation involves the workup and / or purification of amine species, such as toluene diamine (TDA).
[0152] It may be beneficial to treat the alcoholate-rich phase, particularly the second phase, by solid-liquid separation before the first distillation. A preferred solid-liquid separation is extraction, particularly using a non-polar, aprotic solvent such as toluene, benzene, or xylene as the extraction solvent. In a preferred embodiment, toluene is used for extraction. Additional water may be added to reduce the solubility of the alcoholate in the organic solvent layer.
[0153] In addition to or as an alternative to extraction, one or more of the following techniques are used: filtration, centrifugation, decantation.
[0154] The extraction solvent can be recycled to the extraction stage after phase separation.
[0155] Preferably, the first distillation is carried out at a temperature of about 130° C. to about 290° C. and a pressure of about 1 mbar to about 1000 mbar, preferably at a temperature of about 130° C. to about 250° C. and a pressure of about 1 mbar to about 400 mbar, in particular at a temperature of about 140° C. to about 250° C. and a pressure of about 1 mbar to about 200 mbar.
[0156] According to a preferred embodiment, the first distillation comprises a first distillation stage, in which the alcoholic substances are removed by distillation, and a second distillation stage, in which the amine substances are purified by distillation.
[0157] Preferably, the first distillation is performed in one or more distillation columns, such as one or more fractionation columns.
[0158] According to one aspect of the invention, for the first distillation, a fractionation column is used, for example, a fractionation column having 10 to 30 stages, more preferably 15 to 25 stages. According to another aspect of the invention, a sump distillation with a filtration unit in the evaporation loop is used.
[0159] In particular, the first distillation stage is carried out at a temperature of about 130° C. to about 250° C. and a pressure of about 10 mbar to about 1000 mbar.
[0160] The second distillation stage is carried out, for example, at a temperature of about 140° C. to about 250° C. and a pressure of about 1 mbar to about 200 mbar.
[0161] According to another preferred embodiment, the first distillation further comprises a third distillation stage.
[0162] In the embodiment with a third distillation stage, if
[0163] - the first distillation stage is carried out at a temperature of about 60° C. to about 270° C. and a pressure of about 100 mbar to about 1000 mbar; and / or
[0164] - the second distillation stage is carried out at a temperature of about 130° C. to about 250° C. and a pressure of about 10 mbar to about 500 mbar; and / or
[0165] It may be advantageous if the third distillation stage is carried out at a temperature of about 140° C. to about 250° C. and a pressure of about 1 mbar to about 200 mbar.
[0166] According to a further preferred embodiment, the distillation stage of the first distillation in which the amine substances are purified can be carried out completely or partly in a column of an existing amine purification column of an existing amine production plant.
[0167] For example, the second or third distillation stage is carried out by feeding the material to be distilled (i.e., the crude amine material produced from the previous distillation stage) into the existing amine production equipment in an existing amine purification column. This third distillation stage in the existing facility can be carried out in one distillation column (e.g., a dividing wall column), or in another fractionating column, or in a series of several distillation columns.
[0168] In the embodiment in which the amine substance is TDA, the crude amine substance (here: crude TDA) resulting from the corresponding distillation stage of the first distillation can be fed to the fractionation column of the existing TDA plant and can partially or completely form the reactant stream in the corresponding TDA purification.
[0169] For example, crude TDA produced by recovering TDA from polyurethane materials is fed into a tank (e.g., a storage tank) of an existing TDA plant and mixed with additional crude TDA that was not recovered from polyurethane materials. This crude TDA mixture is then preferably further purified by feeding the mixture into a fractionation column.
[0170] In the fractionation column of the TDA apparatus, preferably;
[0171] - withdrawing a low boiler fraction via the top of the column; and / or
[0172] - withdrawing TDA via a side draw in the draw section of the fractionating column; and / or
[0173] - The high-boiling fraction is withdrawn from the bottom of the fractionating tower.
[0174] According to an alternative to withdrawing TDA via a side draw, in particular if prepurified TDA is distilled, the TDA is withdrawn via the top of the fractionating column of the TDA plant after all the DEG fraction has been withdrawn (for example, when the column is used in batch mode). Prepurified TDA is, for example, TDA that is substantially free of light boilers and substantially free of vic-TDA.
[0175] Preferably, in the first distillation, water and / or alcoholic substances are separated from the phase rich in alcoholic substances, in particular the second phase.The water and / or alcoholic substances obtained from the first distillation can be recycled to the phase separation step.
[0176] Furthermore, the present invention relates to a process for producing an isocyanate substance, preferably a toluene diisocyanate (TDI) substance, from an amine substance, preferably a toluenediamine-based substance, obtained by the process according to the invention.
[0177] The advantages and / or features described in conjunction with the process for recovering amine species also apply to the process for producing isocyanate species.
[0178] Preferably, the amine species produced by the recovery process are fed partially or directly to an amine production plant (as described above), an amine storage tank, or a purification section of an isocyanate production plant.
[0179] In order to use the amine species in isocyanate production, the amine species needs to be substantially free of polyol species, residual metals, and silicon compounds.
[0180] Preferably, the amine species is phosgenated so that an isocyanate species is formed.
[0181] In the context of the present invention, the term "isocyanate substance" encompasses all isocyanates known to those skilled in the art in connection with polyurethane chemistry, such as, in particular, toluene diisocyanate (TDI; prepared from toluenediamine (TDA)) or di- and polyisocyanates of the diphenylmethane series (MDI; prepared from diamines and polyamines of the diphenylmethane series (MDA)). The expression "isocyanate substance" also encompasses embodiments in which two or more different isocyanates are used in the preparation of the polyurethane material (e.g., a mixture of MDI and TDI). This also applies to one isocyanate class (that is, for example, also to the various MDI types). The totality of all isocyanates used in the preparation of the polyurethane material is referred to as the isocyanate substance (of the polyurethane material). The isocyanate substance comprises at least one isocyanate.
[0182] In some embodiments, the polyols used in the preparation of polyurethane materials are referred to as polyol materials (polyurethane materials). Polyol materials comprise at least one polyol. Preferably, the polyol materials comprise or are composed of one or more polyols, and these one or more polyols have a molecular weight of approximately 2500 to approximately 3500 grams per mole, a nominal OH functionality of approximately 3, and have an OH value of approximately 48 mg KOH / g to approximately 56 mg KOH / g. Exemplary polyol materials can be the polyol that can be obtained from BASF Corporation (BASF) with the product name Lupranol 2074.
[0183] The present invention further relates to a process for preparing a polyurethane material by reacting a polyol substance obtained by the process according to the present invention with an isocyanate substance, preferably an isocyanate substance obtained by the process according to the present invention.
[0184] In embodiments in which the polyol material obtained by the process according to the invention is used in a process for preparing polyurethane materials, up to 100% of the original polyol can be replaced by the recycled polyol material without significant disadvantages in product quality.
[0185] All advantages and / or features described in conjunction with the process for recovering polyol substances also apply to the process for producing polyurethane materials.
[0186] Preferably, the polyurethane material is used in a mattress or a furniture component or a part of a car seat.
[0187] Further preferred features and / or advantages of the invention form the subject matter of the following description and illustration of exemplary embodiments.
[0188] In the attached figure:
[0189] Figure 1 Schematically illustrating an embodiment of a method for recovering polyol species and / or amine species from end-of-life (eol) polyurethane material by post-processing a mixture resulting from alcoholizing the polyurethane material, wherein the mixture comprises a polyol species-rich phase and an alcoholizing species-rich phase;
[0190] Figure 2 More detailed schematically shows Figure 1 post-treatment of the first phase of the mixture rich in polyol material; and
[0191] Figure 3 More detailed schematically shows Figure 1 Work-up of the second phase of the mixture, which is rich in alcoholated material.
[0192] The same reference numbers are used throughout the drawings to indicate identical or functionally equivalent elements.
[0193] As described above, the embodiments shown in the drawings and described below are exemplary, and other combinations of features are also embodiments of the present invention.
[0194] Figure 1 An exemplary embodiment of a method is shown for recovering polyol species 118 and amine species 122 from end-of-life (eol) polyurethane material 100. The eol polyurethane material 100 is currently polyurethane foam, such as obtained from mattresses or furniture or car seats, for example.
[0195] It should be understood that the steps of recovering the polyol species 118 and the amine species 122 may be performed simultaneously.
[0196] In the alternative, it is also possible to recover only the polyol species 118 or only the amine species 122 .
[0197] The recovery of the polyol material 118 and the recovery of the amine material 122 may also be performed spatially separately and / or sequentially.
[0198] According to the invention, polyurethane materials 100 having a styrene acrylonitrile copolymer (SAN) content of up to 15 wt.-%, based on the total weight of the polyurethane material 100, can be processed by the method. Even polyurethane materials 100 having a SAN content within the aforementioned range can be processed by the method according to the invention despite such a high SAN content.
[0199] According to the presently described embodiment, the polyurethane material 100 is a polyurethane foam, which is prepared by using an isocyanate substance in the form of toluene diisocyanate (TDI).
[0200] Accordingly, the recovered amine species 122 is the corresponding amine, namely toluene diamine (TDA).
[0201] In embodiments in which a polyurethane material 100 made of another isocyanate substance is used, the amine substance respectively comprises or consists of the corresponding amine.
[0202] The polyurethane material 100 is combined with the alcoholizing substance 102 to be alcoholized. Thus, a mixture 108 is formed.
[0203] The alcoholized substance 102 includes or consists of one or more of the following: methanol, ethanol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, methylene glycol, triethylene glycol, glycerol, 2-methyl-1,3-propanediol, and mixtures of two or more thereof.
[0204] For alcoholizing the polyurethane material 100, it is preferred to use about 0.2 parts by weight or more and / or about 5 parts by weight or less of the alcoholizing substance 102 per part by weight of the polyurethane material 100. Preferably, about 0.4 parts by weight or more and / or about 2 parts by weight or less of the alcoholizing substance 102 per part by weight of the polyurethane material 100 is used, particularly about 0.6 parts by weight or more and / or about 1.5 parts by weight or less of the alcoholizing substance 102 per part by weight of the polyurethane material 100, for example, about 0.8 parts by weight or more and / or about 1.2 parts by weight or less of the alcoholizing substance 102 per part by weight of the polyurethane material 100. For an optimized method, additional substances may be added.
[0205] Currently, for the alcoholization of the polyurethane material 100 , a catalyst 104 in the form of potassium hydroxide (KOH) is used.
[0206] In place of potassium hydroxide, good results are obtained if sodium hydroxide (NaOH) is used as catalyst 104 .
[0207] Preferably, the catalyst 104 is used in an amount of about 0.2 wt.-% or more, in particular about 0.4 wt.-% or more, for example about 1 wt.-% or more, based on the total weight of the resulting mixture 108 .
[0208] In particular, the catalyst 104 is used in an amount of about 35 wt.-% or less, preferably about 5 wt.-% or less, such as about 3.5 wt.-% or less, for example about 2 wt.-% or less, based on the total weight of the mixture.
[0209] It may be beneficial if the catalyst 104 is used in an amount of about 0.2 wt.-% or more, preferably about 0.8 wt.-% or more, in particular about 1 wt.-% or more, based on the total weight of the polyurethane material 100 .
[0210] Preferably, the catalyst 104 is used in an amount of 35 wt.-% or less, preferably about 6.5 wt.-% or less, in particular about 5 wt.-% or less, for example about 4 wt.-% or less, based on the total weight of the polyurethane material 100 .
[0211] In an alternative to using potassium hydroxide or sodium hydroxide, catalyst 104 can be selected from the group consisting of other alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carboxylates (particularly acetates), alkaline earth metal carboxylates (particularly acetates), Lewis acids (particularly dibutyltin dilaurate), organic amines (particularly imidazole or diethanolamine), organometallic compounds (particularly rare earth metal catalysts such as titanium tert-butoxide), or tin compounds (such as tin octoate).
[0212] Furthermore, to optimize the release of the amine species 122, the water 106 is currently added in an amount such that the water content of the resulting mixture 108 is from about 0.2 wt.% to about 20 wt.%, particularly from about 3 wt.% to about 8 wt.% water, for example from about 4 wt.% to about 7 wt.% water, based on the total weight of the mixture 108.
[0213] Preferably, the water content is adjusted so that the mixture 108 contains about 1 eq. to about 10 eq., particularly about 1.15 eq. to about 6 eq., for example about 1.3 eq. to about 4 eq., for example about 1.4 eq. to about 2 eq. of water based on the breakable bonds of the polyurethane material 100 .
[0214] Whether to add additional water 106 is determined based on the water content of the polyurethane material 100 at the beginning of the process. This water content is referred to as the "initial water content" of the polyurethane material 100. The initial water content includes previously adsorbed water as well as water included in other ways.
[0215] Specifically, about 1 eq. to about 30 eq. of water 106 , preferably about 10 eq. of water 106 , particularly about 1.15 eq. to about 6 eq., for example about 1.3 eq. to about 4 eq., for example about 1.4 eq. to about 2 eq. of additional water is added based on the breakable bonds of the polyurethane material 100 .
[0216] In embodiments in which a polyurethane material 100 having a relatively high initial water content is used, no or only a small amount of additional water 106 is added before or during the alcoholization.
[0217] In embodiments in which a polyurethane material 100 having an insufficient initial water content is used, 0.2 wt.-% to 30 wt.-%, based on the total weight of the mixture 108 , of additional water 106 is added before or during the alcoholization.
[0218] During the alcoholization of the polyurethane material 100 , an amine species 118 and a polyol species 122 are formed.
[0219] For the alcoholization (i.e., alcoholysis) of the polyurethane material 100, the following reaction conditions have been found to be beneficial:
[0221] - an internal temperature of 150°C or higher, for example about 170°C or higher, and / or about 240°C or lower, in particular about 220°C or lower, for example about 200°C or lower;
[0222] - ambient pressure (e.g., normal pressure at about 1013.25 mbar) or a pressure of up to about 20 bar; and / or
[0223] - Inert gas atmosphere (for example, nitrogen atmosphere), or air.
[0224] In an alternative to carrying out the alcoholysis under an inert gas atmosphere, the alcoholysis can be carried out under air. Optionally, a reflux condenser can be used.
[0225] It may be beneficial if the mixture is degassed using standard techniques before carrying out the alcoholysis.
[0226] The reaction time under reflux and / or the reaction time of the alcoholization reaction is preferably set to about 10 minutes or longer, particularly about 20 minutes or longer, for example about 30 minutes or longer, for example about 40 minutes or longer.
[0227] Preferably, the reaction time under reflux and / or the reaction time of the alcoholization reaction is preferably set to about 200 minutes or less, particularly about 175 minutes or less, such as about 150 minutes or less, for example about 135 minutes or less.
[0228] Particularly in embodiments where the amine species are recovered, it may be beneficial if excess water is removed from the mixture 108, preferably by evaporating the excess water, before allowing the mixture to settle. For example, the mixture 108 may be heated and / or a vacuum may be applied to evaporate the excess water.
[0229] Excess water is removed, for example, by using flash evaporation or by applying a vacuum to the heated mixture 108 .
[0230] For example, the water removal step is performed for about 120 minutes or less, in particular about 90 minutes or less, such as about 75 minutes or less, for example about 60 minutes or less.
[0231] Preferably, the water removal step is performed for about 10 minutes or longer, in particular about 30 minutes or longer, such as about 40 minutes or longer.
[0232] In embodiments where flash evaporation is used to remove water, the removal step (ie, flash evaporation) is performed for 15 minutes or less.
[0233] According to one embodiment, the mixture 108 is contacted with one or more adsorbents 134 (not shown) prior to further processing. For example, the mixture is contacted with a silicate, particularly an alkali metal silicate (e.g., sodium silicate) and / or an alkaline earth metal silicate (e.g., magnesium silicate) prior to further processing.
[0234] Preferably, the mixture is contacted with a silicate (e.g., magnesium silicate), wherein a further mixture of mixture 108 and silicate is prepared. The further mixture preferably comprises from 0.5 wt.% to about 30 wt.% silicate, in particular from about 3 wt.% to about 15 wt.%, for example from about 6 wt.% to about 9 wt.% silicate, based on the total weight of the further mixture. The further mixture is preferably heated under vacuum, preferably at a pressure of about 20 mbar or less, in particular about 10 mbar or less, for example about 5 mbar or less, to a temperature of about 60°C to about 180°C, preferably about 80°C to about 160°C.
[0235] For example, the mixture 108 is contacted with the silicate for about 100 minutes to about 140 minutes.
[0236] According to a preferred embodiment, solids are removed from the mixture 108 by solid-liquid separation 115. For example, the mixture 108 is filtered. As an alternative to or in addition to filtering, solids can be removed by centrifugation and / or decantation.
[0237] For centrifugation, a centrifugal speed of about 2500 rpm to about 14000 rpm, preferably about 3000 rpm to about 6000 rpm, is preferably used. The mixture 108 is preferably centrifuged at a temperature of about 80° C. to about 160° C. The inventors have found that about 4 minutes to about 10 minutes are sufficient for solid-liquid separation 115.
[0238] It may be beneficial to transfer the mixture 108 to a phase separation apparatus for phase separation.
[0239] Thereafter, the mixture 108 is allowed to settle, for example in a phase separation apparatus. To improve the phase separation, it may be beneficial to remove water contained in the mixture 108, for example by flash evaporation, by applying a vacuum to the mixture 108, or by distilling the mixture 108 at atmospheric pressure.
[0240] In addition to or as an alternative to the removal of water, the phase separation can also be improved by adding salts or by using specific internals in the phase separation apparatus.
[0241] Alternatively, phase separation can be promoted by adding a halogenated or non-halogenated hydrocarbon, or a mixture of several halogenated or non-halogenated hydrocarbons, which is immiscible or only partially miscible with the alcoholating material (not further described or illustrated herein).
[0242] In the alternative, a glycol (eg, diethylene glycol) may be added to facilitate phase separation (not shown).
[0243] During settling, the mixture 108 separates into a first phase 110 rich in polyols and a second phase 112 rich in alcoholates. The first phase 110 is an upper phase having a lower density than the second phase 112. The second phase 112 is a lower phase having a higher density than the first phase 110.
[0244] The settling step is carried out at a temperature of the mixture 108 of about 25° C. (room temperature) to about 160° C., preferably about 50° C. to about 150° C., for example about 80° C. to about 120° C. The mixture 108 is maintained at this temperature until phase separation occurs.
[0245] Preferably, no additional solvent is added for phase separation.
[0246] The first phase 110 and the second phase 112 are separated from each other.
[0247] In order to obtain a high-quality polyol material 118 with minimal impurities (eg, potassium, aromatic amines) and a minimum acid value, a post-treatment 116 of the first phase 110 is performed. Figure 2 The post-processing 116 of the first phase 110 is shown in more detail in FIG.
[0248] In embodiments where mixture 108 is a single-phase system, post-processing is preferably performed with mixture 108 as a whole (not shown).
[0249] According to one embodiment, the first phase 110 is contacted with one or more adsorbents 134 (not shown) before further processing. For example, the first phase 110 is contacted with a silicate, particularly an alkali metal silicate (e.g., sodium silicate) and / or an alkaline earth metal silicate (e.g., magnesium silicate) before further processing.
[0250] As an alternative to or in addition to solid-liquid separation 115 prior to phase separation, first phase 110 is currently treated by solid-liquid separation 115 prior to post-treatment 116. In this embodiment, first phase 110 is filtered, preferably using one or more filter membranes having an average mesh size of about 10 μm to about 50 μm. In particular, first phase 110 is filtered through a filter membrane having an average mesh size of about 20 μm or less.
[0251] Filtration is preferably performed by using cascade filters, wherein, for example, the first filter membrane has an average mesh size of about 250 μm to about 290 μm, the second filter membrane has an average mesh size of about 50 μm to about 90 μm, and the third filter membrane has an average mesh size of about 20 μm or less.
[0252] The mentioned filtration conditions are preferred conditions for each filtration used in the process (irrespective of which stage of the process).
[0253] In an alternative to filtration, the first phase 110 can be purified in a centrifuge before further processing and / or decantation. With regard to preferred centrifugation conditions, reference is made to the following description.
[0254] According to the presently described embodiment, post-processing 116 of the first phase 110 includes purifying the first phase 110 by evaporating the first phase 110 using one or more evaporators.
[0255] The evaporation of the first phase 110 in the one or more evaporators is collectively referred to as the second distillation 124 .
[0256] Currently, two evaporators are used in the form of a thin film evaporator 126 followed by a short path evaporator 128 .
[0257] The thin film evaporator 126 is preferably operated at a temperature of about 180°C to about 270°C at a pressure of about 6 mbar to about 20 mbar.
[0258] The short path evaporator 128 is preferably operated at a temperature of about 180°C to about 270°C at a pressure of 0.1 mbar to about 10 mbar.
[0259] In addition to or as an alternative to the thin-film evaporator 126 and the short-path evaporator 128 , there are falling-film evaporators and rotary evaporators.
[0260] After purification by evaporation of the first phase 110 , the first phase 110 is contacted with a cation exchange material 130 and then with an anion exchange material 132 and / or with one or more adsorbents 134 , in particular one or more particulate adsorbents 134 .
[0261] Although currently Figure 2 1. However, the first phase 110 may be contacted with the cation exchange material 130 and the anion exchange material 132 simultaneously or with only one of them.
[0262] As an alternative, the one or more ion exchange materials may be used between two evaporator steps.
[0263] As the cation exchange material 130, a strong acidic material or a weak acidic material can be used. The material can be a polymer resin comprising or consisting of cross-linked polystyrene, polyacrylate or polymethacrylate polymers containing carboxylic acid or sulfonic acid groups. Strong acidic materials containing sulfonic acid groups are preferred. Materials of this type include those available from LANXESS Germany GmbH. K 2431, K 2621 and K 2629, from DuPont TM )of 15. 35 and 40 and C150SH and C160SH from Purolite GmbH, Germany.
[0264] In another embodiment, a weakly acidic material containing a carboxylic acid group is used. Materials of this type include those from DuPont TM )of MAC-3H or from LANXESS Germany GmbH CNP 80.
[0265] As the anion exchange material 132, a weakly basic material or a strongly basic material is used. The material can be a polymer resin composed of cross-linked polystyrene, polyacrylate or polymethacrylate polymer containing tertiary amino groups and / or quaternary amino groups. Strongly basic materials containing quaternary amino groups are preferred. Examples of such materials are from DuPont TM )of HPR 9000OH or available from LANXESS Germany GmbH S 6368A. In another embodiment, a weakly basic material containing a tertiary amino group is used. Examples of such materials are LANXESS Germany GmbH MP 62 or from DuPont TM )of A22.
[0266] As the adsorbent 134, one or more of the following materials are preferably used:
[0267] - activated carbon; and / or
[0268] - silicates, preferably alkali metal silicates or alkaline earth metal silicates or mixtures thereof, for example magnesium silicate and / or sodium silicate; and / or
[0269] -Silicon dioxide.
[0270] Typically, the adsorbent 134 can be a neutral polymer adsorbent or activated carbon. The preferred adsorbent 134 is activated carbon. The activated carbon can be in powder form or granular form. The preferred activated carbon to be used as the adsorbent is chemically activated carbon. Chemically activated carbon can be derived from plant material and activated with phosphoric acid. This type of activated carbon is C GRAN or CNSP 1240 from Norit Activated Carbon or C GRAN 1240 from Calgon Carbon GmbH, Germany. BGE or BGX. Other types of activated carbon may also be used.
[0271] Preferably, the adsorbent(s) 134 are used in an amount of about 0.2 wt.-% to about 20 wt.-%, in particular about 0.3 wt.-% to about 5 wt.-%, based on the total weight of the first phase 110. According to a particularly preferred embodiment, about 0.5 wt.-% to about 3 wt.-% of adsorbent 134, based on the total weight of the mixture between the respective phase 110 and the adsorbent(s) 134, is used.
[0272] In particular, in embodiments where the first phase has been contacted with one or more adsorbents 134 (eg, magnesium silicate) prior to the second distillation 124 , only activated carbon is used as the adsorbent after the second distillation 124 .
[0273] It may also be beneficial to use an adsorbent 134 (eg, a silicate, eg, magnesium silicate) before allowing the mixture 108 to settle prior to phase separation.
[0274] In embodiments where adsorbent 134 is used prior to post-processing the polyol-rich phase, particularly first phase 110, typically only one adsorbent is used for post-processing. Preferably, adsorbent 134 is one that has not been used earlier in the process. For example, activated carbon is used in post-processing the polyol-rich phase, particularly first phase 110.
[0275] Other combinations of the mentioned techniques for post-processing 116 of the first phase 110 are within the scope of the present invention and will be explained in detail in the following detailed examples.
[0276] In particular, after contacting the first phase 110 with the cation exchange material 130 and the anion exchange material 132 and / or the adsorbent 134, a further distillation (referred to as a third distillation) may be performed to remove additional water from the first phase 110. The further distillation is not illustrated. For the third distillation, it is preferred to use one or more evaporators, such as a thin film evaporator, a short path evaporator, a falling film evaporator, a rotary evaporator, or a mixture of two or more thereof.
[0277] As described, in an alternative arrangement in which one or more evaporators are used at the beginning and optionally again at the end of the workup, it is also possible to first contact the first phase 110 with one or more adsorbents 134 and / or cation exchange materials 130 and anion exchange materials 132 and then evaporate only the first phase 110 (in the second distillation 124) (not shown).
[0278] After post-processing 116, the first phase 110 preferably has one or more of the following characteristics:
[0279] a potassium content of about 0.1 wt.-% or less, preferably about 0.01 wt.-% or less, for example about 0.005 wt.-% or less, based on the total weight of the first phase 110 ;
[0280] - a content of alcoholic substances 102 of about 0.15 wt.-% or less, based on the total weight of the first phase 110 after post-treatment 116 ;
[0281] - an aromatic amine content of about 0.03 wt.-% or less, preferably about 0.01 wt.-% or less, based on the total weight of the first phase 110 after post-treatment 116;
[0282] - a polyol substance content of about 97 wt.-% or more, in particular about 99 wt.-% or more, based on the total weight of the first phase 110 after post-treatment 116;
[0283] -Acid value of 0.1 mg KOH / g or less.
[0284] The acid number is determined based on DIN EN ISO 4629-2 (with two minor variations). A 1:1 mixture of isopropanol / water is used as the solvent mixture instead of a 2:1 mixture of toluene / ethanol. As a further variation, the NaOH / KOH is dissolved in methanol instead of ethanol. In the context of the present invention, the acid number relates to the total acid number of the corresponding substance, also referred to as the acid value.
[0285] To determine the potassium content, an automated wet chemical digestion was performed, followed by determination of the potassium content by ICP / OES (Inductively Coupled Plasma / Optical Emission Spectroscopy).
[0286] The content of aromatic amines is determined using liquid chromatography. For example, 0.01 g of the sample to be analyzed (or 0.5 g if very low amounts of aromatic amines are present in the sample) is diluted with 20 ml of acetonitrile and filtered through a filter with a 0.2 μm mesh size. The resulting mixture is then injected into a reverse phase (RP) high pressure liquid chromatograph (HPLC) with ultraviolet (UV) detection.
[0287] Calibration solutions of the corresponding aromatic amines were prepared and a calibration curve was constructed using a 5-point calibration.
[0288] A reverse phase column with silica particles having a particle size of 3.5 μm and a pore size of 100 angstroms was used.
[0289] The response factors were determined by dividing the corresponding peak areas by the calibration mass concentrations.
[0290] Using the response factor, determine the concentration of the amine compound.
[0291] The OH number (corresponding to the OH value) was determined based on DIN EN ISO 4629-2, but using 4-pyrrolidinyl-pyridine instead of DMAP.
[0292] The water content was determined by Karl-Fischer titration. Approximately 15 ml of anhydrous methanol was added to the titration flask, and Karl Fischer reagent was added to the determined endpoint. The substance was added quickly, stirred for one minute, and titrated again with Karl Fischer reagent to the endpoint.
[0293] The content of alcoholized substance 102 (here: diethylene glycol (DEG)) was determined by gas chromatography. Approximately 0.4 to 0.8 g of sample was diluted in 15 to 20 ml of a 1:1 mixture of ethyl acetate and methanol, with undecane added as an internal standard. Five to six drops of this mixture were reacted with 1 to 1.5 ml of N-methyl-N-trimethylsilyl-trifluoroacetamide (MSTFA), and the sample was injected into a gas chromatograph (GC) equipped with flame ionization detection (FID). The internal standard was used for quantification, and two consecutive runs were performed.
[0294] The content of polyol substances was determined by GPC (gel permeation chromatography). In this respect, tetrahydrofuran was used as eluent. As solvent, a mixture of tetrahydrofuran and toluene was used as internal standard.
[0295] For GPC, use A column of styrene divinylbenzene with an average pore size of 5 angstroms and an average particle size of 5 μm was used. One precolumn with a height of 5 cm and two columns with a height of 30 cm were used.
[0296] Afterwards, UV / Vis (ultraviolet / visible) spectroscopy was performed, wherein calibration was performed using PEG (polyethylene glycol) standards available from PSS GmbH, 55120 Mainz, Germany. Based on the obtained UV / Vis data, the relative The polyol content was determined by calibration of the area integral of 2074 (a trifunctional polyether polyol containing mainly secondary hydroxyl groups). 2074 is commercially available from BASF Polyurethanes GmbH, 49448 Lemförde, Germany.
[0297] Potassium ion content was determined using inductively coupled plasma atomic emission spectrometry. Samples were pretreated with acid prior to analysis.
[0298] As for the workup 120 of the second phase 112, the distillate of the second distillation 124 carried out during the workup 116 of the first phase 110 is now combined with the second phase 112 (see Figure 3 ).
[0299] Solids can be removed from the second phase 112 by solid-liquid separation 115 before further workup 120. This is particularly preferred in embodiments in which no solid-liquid separation 115 is performed on the mixture 108.
[0300] The solid-liquid separation 115 is preferably filtration, decantation, centrifugation, or a combination of two or more thereof.
[0301] For further preferred conditions for solid-liquid separation 115 , reference is made to the above description. These conditions are also effective for removing solids from the second phase 112 .
[0302] Alternatively, solid-liquid separation 115 may be extraction. The extraction is performed using an aprotic, non-polar organic solvent (e.g., toluene, benzene, xylene, etc.). In a preferred embodiment, the extraction is performed using toluene. In order to reduce the solubility of the alcoholized substance 102 in the organic solvent layer, additional water may have to be added.
[0303] The resulting organic solvent-rich layer is further processed in a first distillation step (referred to as first distillation 136). The aqueous layer containing alcoholate material 102 and inorganic components is further processed in an evaporation step to recover alcoholate material 102, water, and trace amounts of extraction solvent. The resulting stream is fed back to the phase separation step (e.g., Figure 1 The remaining solids containing inorganic salts and other impurities generated by additives used to prepare the polyurethane material (e.g., silicone, catalysts, pigments, etc.) are discarded.
[0304] Therefore, a distillation (referred to as the first distillation 136 ) is performed, thereby obtaining the amine substance 122 (currently TDA).
[0305] The first distillation 136 comprises one or more distillation stages 136a, 136b, 136c. Figure 3 In FIG, three distillation stages are shown. However, according to the invention, it is also possible to include only one or two distillation stages in the process (as will be described below).
[0306] In particular, no separate hydrolysis of the second phase 112 is performed.
[0307] In a first embodiment in which no extraction 115 is performed, the first distillation 136 as a whole is performed at a temperature of about 130° C. to about 290° C. and a pressure of about 1 mbar to about 1000 mbar, preferably at a temperature of about 130° C. to about 250° C. and a pressure of about 1 mbar to about 400 mbar, in particular at a temperature of about 140° C. to about 250° C. and a pressure of about 1 mbar to about 200 mbar.
[0308] Also in embodiments where no extraction is performed, first distillation 136 is performed in one or more distillation columns (eg, fractionation columns).
[0309] According to a second embodiment in which no extraction is performed, the first distillation stage 136a can be carried out, for example, at a temperature of about 130° C. to about 260° C. and a pressure of about 500 mbar to about 1000 mbar to remove water. In a preferred variant, the first distillation stage 136a is carried out at a bottom temperature of 256° C. and a pressure of 1000 mbar and at a reflux ratio (in tons / ton) of 1.
[0310] In the second distillation stage 136 b, alcoholate 102 is removed, for example, by distillation at a temperature of about 140° C. to about 250° C. and a pressure of about 10 mbar to about 500 mbar, preferably at about 10 mbar to 250 mbar and a bottom temperature of about 140° C. to about 230° C. In the case of diethylene glycol removal, this distillation sequence results in a residual diethylene glycol content of about 0 ppm to about 400 ppm at a reflux ratio of 1.
[0311] In the third distillation stage 136c, the amine species are further purified, for example, by conducting the distillation stage 136c at a temperature of about 140°C to about 250°C and a pressure of about 1 mbar to about 200 mbar.
[0312] In yet another embodiment, distillation stages 136a and 136b are performed as a combined distillation, removing water and alcoholic material 102 in one distillation column.
[0313] The first distillation stage 136a can be carried out at a pressure of about 50 mbar to about 500 mbar, preferably about 50 mbar to about 200 mbar, and a bottom temperature of about 170° C. to about 250° C., preferably about 170° C. to about 220° C. The distillation to remove diethylene glycol and water is carried out, for example, in a bottom distillation, with filtration being carried out in the evaporation loop.
[0314] In the second distillation stage 136 b , the remaining alcoholized substances 102 are removed in a packed or plate distillation column at a temperature of about 150° C. to about 250° C., preferably about 170° C. to about 220° C., and at a pressure of about 10 mbar to about 500 mbar, preferably about 10 mbar to about 200 mbar.
[0315] In the third distillation stage 136c, the amine species are purified by distilling the amine species at about 1 mbar to about 200 mbar, preferably about 1 mbar to 100 mbar, and at a bottom temperature of about 140°C to about 250°C.
[0316] According to the embodiment in which the extraction of the second phase 112 with a non-polar aprotic solvent has already been carried out before the distillation 136, the first distillation 136 as a whole is preferably carried out at a temperature of about 130° C. to about 290° C., preferably about 130° C. to about 250° C., in particular about 140° C. to about 250° C. The first distillation 136 as a whole is preferably carried out at a pressure of about 1 mbar to about 1000 mbar, in particular about 1 mbar to about 400 mbar, for example about 1 mbar to about 200 mbar.
[0317] Preferably, the first distillation 136 is performed in one or more distillation columns (eg, one or more fractionation columns).
[0318] The inventors have found that optimized results are achieved if in the first distillation stage 136a of the first distillation 136 the non-polar aprotic solvent, such as toluene, and residual alcoholic substances, such as diethylene glycol (DEG), are removed.
[0319] The first distillation stage 136a can be conducted, for example, at a temperature of about 130°C to about 250°C and a pressure of about 10 mbar to about 1000 mbar to remove toluene and DEG.
[0320] In the second distillation stage 136b, the amine species is further purified, for example, by distillation at a temperature of about 140°C to about 250°C and a pressure of about 1 mbar to about 200 mbar.
[0321] The second distillation step can be accomplished using existing facilities of an existing TDA plant.
[0322] Independently of the variant of the first distillation 136 , the alcoholic substances and water removed by distillation can be recycled to the phase separation step.
[0323] In embodiments where extraction has been performed, the corresponding extraction solvent (e.g., a non-polar aprotic solvent) may be recycled to the extraction step (e.g., by Figure 3 (as indicated by the dotted arrow in ).
[0324] Regardless of the variant according to which the first distillation 136 is performed, at least the final distillation stage, according to which the amine substance 122 is purified, can be performed in an existing fractionation column 140 of an existing amine production plant. Figure 3 Indicated graphically by a dotted line.
[0325] In embodiments where the amine material 122 is TDA, the crude TDA produced from the previous distillation stages 136a, 136b of the first distillation 136 is typically fed to the fractionation column 140 of the existing amine production facility. The fractionation column 140 is preferably a dividing wall column.
[0326] For example, crude TDA is used as the reactant stream and fed into the feed section of a dividing wall column (not shown). The crude TDA produced from the first distillation stage 136a or the second distillation stage 136b can form the reactant stream as a whole or be combined with more crude TDA produced, for example, by hydrogenation of dinitrotoluene.
[0327] The crude TDA or crude TDA mixture resulting from the first distillation is then preferably further purified by feeding the mixture to a fractionation column.
[0328] According to a preferred embodiment, the low boiler fraction is withdrawn via the top of column 140. Purified TDA is withdrawn via a side draw in the draw section of column 140. The high boiler fraction is preferably withdrawn via the bottom of column 140.
[0329] More details about typical TDA purification processes in existing TDA plants can be found in, for example, EP 1706370, EP 1746083 and EP 1864969. The content of the mentioned applications shall be fully incorporated into the present application.
[0330] Due to and / or after the post-treatment 120 of the second phase 112, the second phase 112 has a content of aromatic amines (i.e., amine substances) of 6.5 wt.% or more, in particular 15 wt.% or more, based on the total weight of the second phase 112 after the post-treatment 120.
[0331] Preferably, a polyol substance release yield of about 93% or more, particularly about 94% or more, can be obtained.
[0332] In particular, an amine species release yield of about 70% or more, particularly about 85% or more, can be obtained.
[0333] The release yield of the polyol substance is determined by dividing the amount of the polyol substance quantified after the alcoholization step in the two layers by the amount of the polyol substance theoretically obtainable from the polyurethane material 100 .
[0334] The release yield of the amine species is determined by dividing the amount of the amine species quantified after the post-treatment 120 by the amount of the amine species theoretically obtainable from the polyurethane material 100 .
[0335] By means of the above-described method steps, high-quality polyol substances 118 and / or high-quality amine substances 122 can be recovered from the polyurethane material 100 , in particular the polyurethane foam.
[0336] The recovered polyol material 118 is preferably used to prepare a polyurethane material, such as polyurethane foam. Therefore, the polyol material 118 obtained by the above-described method is reacted with an isocyanate material (not shown).
[0337] The polyurethane material produced can be used in mattresses or furniture components or car seats.
[0338] The recovered amine species 122 (currently TDA) is preferably used to produce an isocyanate species (currently TDI) (not shown).
[0339] To this end, TDA can be fed to a TDA plant (e.g. Figure 3 Indicated by the diagram in the figure), in the TDA storage tank or in the phosgenation section of the TDI equipment.
[0340] For example, amine material 122 is phosgenated to produce TDI.
[0341] The TDI produced can be used as an isocyanate material to produce polyurethane foam by reacting it with a polyol material 118 or any other suitable polyol component.
[0342] Hereinafter, preferred examples are described in detail:
[0343] For all examples described below, the wt.-% are given relative to the corresponding mixture, equal total weight.
[0344] For these examples, polyurethane foam was used. For the release yield, the following expected values, i.e., theoretically achievable amounts, were used:
[0345] - 65 wt.-% of foam as polyol
[0346] - 23 wt.-% of the foam as toluenediamine.
[0347] The remaining amount is mainly composed of additives and losses due to carbon dioxide formation during hydrolysis. It is expected that the polyurethane material contains about 2 moles of functional groups per kg (kilogram) of polyurethane material. In this aspect, the functional groups are urethane groups and urea groups.
[0348] In the following, different examples of cracking and phase separation experiments are described. Subsequently, examples of post-treatment of a polyol material and an example of post-treatment of an amine material are described, starting from one of the cracking and phase separation examples. In the overall recovery process (recovery of a polyol material or recovery of an amine material or both), cracking and phase separation are combined with one or more corresponding post-treatments.
[0349] In the context of this specification and the appended claims, the term "cleaving" means contacting the polyurethane material with an alcoholizing substance, and according to some examples, with water.
[0350] Next, Examples 11 to 13 are provided, which describe simulations of the process, including hydroglycolysis and an exemplary first distillation.
[0351] Examples of cleavage and phase separation:
[0352] It should be noted that for some examples no further workup was performed. For other examples only a short workup was performed, which is described together with the cleavage and phase separation.
[0353] Example 1:
[0354] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0355] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0356] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 24 h while maintaining the temperature at about 80° C. After 24 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholated species).
[0357] Soon after phase separation, the first phase contained 80 wt.-% polyol, 10 wt.-% DEG, 3.07 wt.-% aromatic amine and 0.024 wt.-% potassium.
[0358] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 72 wt.-% DEG, 8.56 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0359] During the cleavage and phase separation according to Example 1, 80% of the polyol and 57% of the amine could be released.
[0360] Example 2:
[0361] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0362] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0363] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0364] Soon after phase separation, the first phase contained 79 wt.-% polyol, 11 wt.-% DEG, 3.52 wt.-% aromatic amine and 0.029 wt.-% potassium.
[0365] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 62 wt.-% DEG, 9.82 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0366] During the cleavage and phase separation according to Example 2, 90% of the polyol and 59% of the amine could be released.
[0367] Example 3:
[0368] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0369] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 190° C. under nitrogen at ambient pressure with a reflux condenser for 5 h.
[0370] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0371] Shortly after phase separation, the first phase contained 76 wt.-% polyol, 12 wt.-% DEG, 3.32 wt.-% aromatic amine and 0.025 wt.-% potassium.
[0372] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 68 wt.-% DEG, 8.87 wt.% aromatic amine, and 1.5 wt.-% potassium.
[0373] During the cleavage and phase separation according to Example 3, 84% of the polyol and 56% of the amine could be released.
[0374] Example 4.1:
[0375] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0376] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0377] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 24 h while maintaining the temperature at about 80° C. After 24 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholated species).
[0378] Soon after phase separation, the first phase contained 78 wt.-% polyol, 12 wt.-% DEG, 2.98 wt.-% aromatic amine and 0.022 wt.-% potassium.
[0379] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 69 wt.-% DEG, 7.81 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0380] During cleavage and phase separation according to Example 4.1, 95% of the polyol and 50% of the amine could be released.
[0381] Example 4.2:
[0382] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0383] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0384] Thereafter, the mixture was cooled to 140° C. and allowed to settle for 12 h while maintaining the temperature at about 140° C. After 12 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0385] Shortly after phase separation, the first phase contained 78 wt.-% polyol, 12 wt.-% DEG, 2.98 wt.-% aromatic amine and 0.022 wt.-% potassium.
[0386] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 69 wt.-% DEG, 7.81 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0387] During cleavage and phase separation according to Example 4.2, 95% of the polyol and 50% of the amine could be released.
[0388] Example 4.3:
[0389] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0390] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0391] The mixture was then cooled to 90° C. and centrifuged at 4000 rpm for 5 minutes. After centrifugation, phase separation occurred, forming a first phase (upper layer rich in polyol substances) and a second phase (lower layer rich in alcoholized substances).
[0392] Shortly after phase separation, the first phase contained 78 wt.-% polyol, 12 wt.-% DEG, 2.98 wt.-% aromatic amine and 0.022 wt.-% potassium.
[0393] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 69 wt.-% DEG, 7.81 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0394] Example 4.4:
[0395] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0396] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% potassium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0397] The mixture was then cooled to 120° C. and centrifuged at 4000 rpm for 5 minutes. After centrifugation, phase separation occurred, forming a first phase (upper layer rich in polyol substances) and a second phase (lower layer rich in alcoholized substances).
[0398] Likewise, centrifugation at 4000 rpm for 5 minutes at 140°C resulted in successful phase separation.
[0399] Shortly after phase separation, the first phase contained 78 wt.-% polyol, 12 wt.-% DEG, 2.98 wt.-% aromatic amine and 0.022 wt.-% potassium.
[0400] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 69 wt.-% DEG, 7.81 wt.% aromatic amine, and 1.6 wt.-% potassium.
[0401] During cleavage and phase separation according to Example 4.4, 95% of the polyol and 50% of the amine could be released.
[0402] Example 5:
[0403] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0404] Afterwards, a mixture of 48 wt.% eol polyurethane foam, 48 wt.% diethylene glycol (DEG), 1.0 wt.% potassium hydroxide as catalyst, and 3.0 wt.% water was formed. The mixture was stirred at 170° C. under nitrogen at ambient pressure with a reflux condenser for 2 h.
[0405] After the mixture had been reacted using a reflux condenser for 1 h, distillation was performed at about 170° C. to 190° C. for 60 minutes in order to partially remove excess water.
[0406] Thereafter, the mixture was cooled to 80° C. and allowed to settle for 15.5 h while maintaining the temperature at about 80° C. After 15.5 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0407] Shortly after phase separation, the first phase contained 81 wt.-% polyol, 13.1 wt.-% DEG, 5.7 wt.-% aromatic amine and less than 0.021 wt.-% potassium.
[0408] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 75.4 wt.-% DEG, 13.8 wt.% aromatic amine, and 1.2 wt.-% potassium.
[0409] During the cleavage and phase separation according to Example 5, more than 95% of the polyol and 86% of the amine could be released.
[0410] Example 6:
[0411] The Eol mattresses are classified so that the Eol polyurethane foam is obtained.
[0412] Afterwards, a mixture of 49.25 wt.% eol polyurethane foam, 49.25 wt.% diethylene glycol (DEG) and 1.5 wt.% sodium hydroxide as catalyst (without additional water) was formed. The mixture was stirred at 200° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 h.
[0413] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0414] Shortly after phase separation, the phases were filtered and the composition of the filtrate was determined. Accordingly, the first phase contained 79 wt.-% polyol, 14 wt.-% DEG, 3.91 wt.-% aromatic amine and less than 3 wt.-% potassium.
[0415] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 64 wt.-% DEG, 8.04 wt.% aromatic amine, and 0.1 wt.-% potassium.
[0416] During the cleavage and phase separation according to Example 6, 95% of the polyol and 46% of the amine could be released.
[0417] Example 6 shows that sodium hydroxide can be used as a catalyst.
[0418] Example 7:
[0419] An eol polyurethane foam containing 15 wt.-% styrene-acrylonitrile resin (SAN) obtained from an eol mattress is provided.
[0420] A mixture of 49.50 wt.% of the eol polyurethane foam, 41.25 wt.% of diethylene glycol (DEG), 1.5 wt.% of potassium hydroxide as a catalyst, and 7.5 wt.% of additional water was then formed. The additional water was added after the remaining components had been heated to 200° C. After the additional water was added, the temperature of the mixture was lowered to 140° C. The mixture was then stirred at 140° C. under nitrogen at ambient pressure with a reflux condenser for 2 hours.
[0421] After the mixture had been reacted using a reflux condenser for 2 h, distillation was performed for 45 minutes in order to remove excess water.
[0422] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0423] The first layer was filtered using a filter element having a pore size of approximately 20 μm.
[0424] After filtration, the first phase contained 59 wt.-% polyol, 19 wt.-% DEG, 8.40 wt.-% aromatic amine, 0.044 wt.-% potassium and 0.4 wt.-% water.
[0425] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 51 wt.-% DEG, 13.81 wt.% aromatic amine, and 0.1 wt.-% potassium.
[0426] During the cleavage and phase separation according to Example 7, 93% of the polyol and 80% of the amine could be released.
[0427] Example 8:
[0428] A model polyurethane foam comprising polyol (65 wt.-% of the foam) and toluenediamine (23 wt.-% of the foam) was used as the eol polyurethane foam for this example.
[0429] A mixture of 29.5 wt.% eol polyurethane foam, 60.0 wt.% diethylene glycol (DEG), 0.5 wt.% potassium hydroxide as a catalyst, and 10 wt.% additional water was formed. The additional water was added after the remaining components had been heated to 220° C. After the additional water was added, the temperature of the mixture was lowered to 120° C. The mixture was then stirred at 120° C. under nitrogen at ambient pressure with a reflux condenser for 2.5 hours.
[0430] After the mixture had been reacted using a reflux condenser for 2.5 h, distillation was performed for 60 minutes to remove excess water.
[0431] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0432] The first layer was filtered using a filter element having a pore size of approximately 20 μm.
[0433] After filtration, the first phase contained 79 wt.-% polyol, 16 wt.-% DEG, 3.98 wt.-% aromatic amine, 0.0009 wt.-% potassium and 0.3 wt.-% water.
[0434] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 77 wt.-% DEG, 9.24 wt.% aromatic amine, and 0.53 wt.-% potassium.
[0435] During the cleavage and phase separation according to Example 8, 90% of the polyol and 91% of the amine could be released.
[0436] Example 9:
[0437] A model polyurethane foam comprising polyol (65 wt.-% of the foam) and toluenediamine (23 wt.-% of the foam) was used as the eol polyurethane foam for this example.
[0438] A mixture of 46.25 wt.% eol polyurethane foam, 47.5 wt.% diethylene glycol (DEG), 1.25 wt.% potassium hydroxide as a catalyst, and 5 wt.% additional water was formed. The additional water was added after the remaining components had been heated to 220° C. After the additional water was added, the temperature of the mixture was lowered to 160° C. The mixture was then stirred at 160° C. under nitrogen at ambient pressure with a reflux condenser for 1.75 h.
[0439] After the mixture had been reacted using a reflux condenser for 1.75 h, distillation was performed for 30 minutes to remove excess water.
[0440] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0441] The first phase is filtered using a filter element having a pore size of approximately 20 μm.
[0442] After filtration, the first phase contained 74 wt.-% polyol, 16 wt.-% DEG, 6.7 wt.-% aromatic amine, 0.0065 wt.-% potassium and 0.3 wt.-% water.
[0443] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 67 wt.-% DEG, 14.59 wt.% aromatic amine, and 1.5 wt.-% potassium.
[0444] During the cleavage and phase separation according to Example 9, 96% of the polyol and 89% of the amine could be released.
[0445] Example 10:
[0446] A model polyurethane foam comprising polyol (65 wt.-% of the foam) and toluenediamine (23 wt.-% of the foam) was used as the eol polyurethane foam for this example.
[0447] A mixture of 34.7 wt.% eol polyurethane foam, 60.0 wt.% diethylene glycol (DEG), 2.0 wt.% potassium hydroxide as a catalyst, and 3.3 wt.% additional water was formed. The additional water was added after the remaining components had been heated to 200° C. After the additional water was added, the temperature of the mixture was lowered to 170° C. The mixture was then stirred at 170° C. under nitrogen at ambient pressure with a reflux condenser for 1.67 h.
[0448] Afterwards, the mixture was cooled to 80° C. and allowed to settle for 16 h while maintaining the temperature at about 80° C. After 16 h, phase separation occurred to form a first phase (upper layer rich in polyol species) and a second phase (lower layer rich in alcoholized species).
[0449] The first phase is filtered using a filter element having a pore size of approximately 20 μm.
[0450] After filtration, the first phase contained 78.5 wt.-% polyol, 15 wt.-% DEG, 4.83 wt.-% aromatic amine, 0.0165 wt.-% potassium and 0.5 wt.-% water.
[0451] Shortly after phase separation, the second phase contained less than 5 wt.-% polyol, 75 wt.-% DEG, 9.0 wt.% aromatic amine, and 1.7 wt.-% potassium.
[0452] During the cleavage and phase separation according to Example 10, 99% of the polyol and 90% of the amine could be released.
[0453] Example of post-treatment of the phase rich in polyol substances, currently the first phase:
[0454] Example 1A1:
[0455] For Example 1A1, the first phase of Example 1 was used as the starting material.
[0456] In order to deposit the solid in the first phase, the deposition was carried out for 24 h. In this respect, the first phase was stored in the storage tank for 24 h.
[0457] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0458] After filtration, the first phase contained 82 wt.-% polyol, 11.1 wt.-% DEG, 3.2 wt.-% aromatic amine and 0.016 wt.-% potassium.
[0459] After filtration, the first phase was evaporated in a thin-film evaporator at 250° C. and a pressure of 7 mbar and subsequently in a short-path evaporator at 250° C. and a pressure of 0.1 mbar.
[0460] The first phase then contains 99 wt.-% polyol, less than 0.1 wt.-% DEG, 0.018 wt.-% aromatic amine, 0.052 wt.-% potassium, and an acid value of less than 0.01 mg KOH / g.
[0461] In the next step, a cation exchange material (5 wt.-% of a strongly acidic resin material having sulfonic acid groups, here: having the trade name A product of K 2621, available from LANXESS Germany GmbH, was contacted with the first phase in a stirred reactor at 80° C. for 24 h and filtered using a filter with a pore size of about 70 μm to obtain a composition of more than 99 wt.% polyols, less than 0.006 wt.% aromatic amines, less than 0.1 wt.% diethylene glycol, and 0.0015 wt.% potassium. The acid number was 0.12 mg KOH / g.
[0462] In the next step, an anion exchange material (2 wt.-% of a strongly basic resin material based on a styrene divinylbenzene copolymer, which is available from LANXESS Germany GmbH under the product name S 6368) was placed in contact with the first phase in a stirred reactor at 80°C for 24 h and filtered using a filter with a pore size of about 70 μm.
[0463] Afterwards, water was removed by distillation of the first phase at 110° C. under a pressure of 10 mbar, resulting in a composition of more than 99 wt.-% polyols, a DEG content below the detection limit, less than 0.006 wt.-% aromatic amines, 0.0015 wt.-% potassium and an acid number of 0.08 mg KOH / g.
[0464] Example 1A2:
[0465] For Example 1A2, the first phase of Example 1 was used as the starting material.
[0466] In order to deposit the solid in the first phase, the deposition was carried out for 24 h. In this respect, the first phase was stored in the storage tank for 24 h.
[0467] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0468] After filtration, the first phase contained 82 wt.-% polyol, 11.1 wt.-% DEG, 3.2 wt.-% aromatic amine and 0.016 wt.-% potassium.
[0469] After filtration, the first phase was evaporated in a thin-film evaporator at 250° C. and a pressure of 7 mbar and subsequently in a short-path evaporator at 250° C. and a pressure of 0.1 mbar.
[0470] The first phase then contains 99 wt.-% polyol, less than 0.1 wt.-% DEG, 0.018 wt.-% aromatic amine, 0.052 wt.-% potassium, and an acid value of less than 0.01 mg KOH / g.
[0471] In a next step, the first phase is contacted with 5 wt.-% of micronized magnesium silicate (currently micronized magnesium silicate with the trade name Ambosol MP 20, available from PQ France SAS, 60350 Trosly-Breuil, France), 5 wt.-% of activated carbon (currently available under the trade name CNSP 1240) and 2 wt.-% of water under stirring at 110° C. and 10 mbar for 1 h, then under full vacuum, which is reached at 4 mbar after 3 hours, for a further 3 hours.
[0472] Afterwards, the mixture was filtered using a filter with a pore size of 70 μm to obtain a composition of more than 99 wt.-% polyols, less than 0.1 wt.-% DEG, less than 0.008 wt.-% aromatic amines, less than 0.0003 wt.-% potassium and an acid value of 0.04 mg KOH / g.
[0473] Example 1A3:
[0474] For Example 1A3, the first phase of Example 1 was used as the starting material.
[0475] In order to deposit the solid in the first phase, the deposition was carried out for 24 h. In this respect, the first phase was stored in the storage tank for 24 h.
[0476] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0477] After filtration, the first phase contained 82 wt.-% polyol, 11.1 wt.-% DEG, 3.2 wt.-% aromatic amine and 0.016 wt.-% potassium.
[0478] After filtration, the first phase was evaporated in a thin-film evaporator at 250° C. and a pressure of 7 mbar and subsequently in a short-path evaporator at 250° C. and a pressure of 0.1 mbar.
[0479] The first phase then contains 99 wt.-% polyol, less than 0.1 wt.-% DEG, 0.018 wt.-% aromatic amine, 0.052 wt.-% potassium, and an acid value of less than 0.01 mg KOH / g.
[0480] In a next step, the first phase is contacted with 5 wt.-% of micronized magnesium silicate (currently micronized magnesium silicate with the trade name Ambosol MP 20, available from PQ France S.A., Trosly-Breuil 60350, France), and 2 wt.-% of water while stirring at 80° C. for 1 h and filtered using a filter with a pore size of about 70 μm.
[0481] Afterwards, water was removed by distillation at 110° C. and a pressure of 10 mbar, resulting in a composition of more than 99 wt.-% polyols, less than 0.1 wt.-% DEG, less than 0.02 wt.-% aromatic amines, less than 0.0003 wt.-% potassium and an acid number of 0.04 mg KOH / g.
[0482] Comparison of Example 1A2 and Example 1A3 shows that significantly more aromatic amines can be removed with the combination of magnesium silicate and activated carbon than with magnesium silicate alone.
[0483] Example 2A1:
[0484] For Example 2A1, the first phase of Example 2 was used as the starting material.
[0485] In order to deposit the solid in the first phase, the deposition was carried out for 10 h. In this respect, the first phase was stored in the storage tank for 10 h.
[0486] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0487] After filtration, the first phase contained 79 wt.-% polyol, 10.7 wt.-% DEG, 3.5 wt.-% aromatic amine and 0.025 wt.-% potassium.
[0488] After filtration, the first phase was evaporated in a thin-film evaporator at 200° C. and a pressure of 7 mbar and subsequently in a short-path evaporator at 200° C. and a pressure of 7 mbar.
[0489] The first phase then contained 99 wt.-% polyol, 0.21 wt.-% DEG, 0.25 wt.-% aromatic amine and 0.045 wt.-% potassium. The acid value was below 0.01 mg KOH / g.
[0490] In the next step, a cation exchange material (9 wt.-% of a strongly acidic resin material having sulfonic acid groups, here: having the trade name A product of K 2629, available from LANXESS Germany GmbH, was contacted with the first phase in a stirred reactor at 80° C. for 24 h and filtered using a filter having a pore size of about 70 μm to obtain a composition of more than 99 wt.% polyol, 0.21 wt.% DEG, less than 0.006 wt.% aromatic amine, and 0.0010 wt.% potassium. The acid number was 0.63 mg KOH / g.
[0491] Thereafter, the first phase is mixed with an anion exchange material in the form of a weakly basic macroporous anion exchange resin having tertiary amine groups (monofunctional) (available under the trade name MP 62 (available from LANXESS Germany GmbH). A mixture of the first phase and 18 wt.% of anion exchange material was prepared, stirred at 80° C. for 24 h, and filtered using a filter with a pore size of approximately 70 μm. This step of contacting the first phase with the anion exchange material was performed twice (fresh anion exchange material was used for each repetition).
[0492] The first phase was then distilled at 110° C. using a pressure of 10 mbar to remove water, resulting in a composition comprising 99 wt.% polyol, 0.13 wt.% DEG, less than 0.006 wt.% aromatic amine and 0.001 wt.% potassium. The acid number was 0.04 mg KOH / g.
[0493] Example 2A2:
[0494] For Example 2A2, the first phase of Example 2 was used as the starting material.
[0495] In order to deposit the solid in the first phase, the deposition was carried out for 10 h. In this respect, the first phase was stored in the storage tank for 10 h.
[0496] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0497] After filtration, the first phase contained 79 wt.-% polyol, 10.7 wt.-% DEG, 3.5 wt.-% aromatic amine and 0.025 wt.-% potassium.
[0498] After filtration, the first phase was evaporated in a thin-film evaporator at 200° C. and a pressure of 7 mbar and subsequently in a short-path evaporator at 200° C. and a pressure of 7 mbar.
[0499] The first phase then contained 99 wt.-% polyol, 0.21 wt.-% DEG, 0.25 wt.-% aromatic amine and 0.045 wt.-% potassium. The acid value was below 0.01 mg KOH / g.
[0500] In the next step, the first phase is contacted with an activated carbon material. A mixture of the first phase and 5 wt.% activated carbon (currently available under the trade name CNSP 1240) is prepared. The mixture is stirred at 80°C for 1 hour and filtered using a filter with a pore size of approximately 70 μm. Water is then removed by distillation at 110°C and 10 mbar, resulting in a composition comprising 99 wt.% polyol, 0.21 wt.% DEG, less than 0.0075 wt.% aromatic amine, and 0.0039 wt.% potassium. The acid number is 0.09 mg KOH / g.
[0501] Comparison of Example 2A2 with Example 1A2 shows that magnesium silicate appears to be more effective in potassium removal than activated carbon alone.
[0502] Example 3A1:
[0503] For Example 3A1, the first phase of Example 3 was used as the starting material.
[0504] In order to deposit the solid in the first phase, the deposition was carried out for 24 h. In this respect, the first phase was stored in the storage tank for 24 h.
[0505] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0506] After filtration, the first phase contained 80 wt.-% polyol, 11.5 wt.-% DEG, 3.3 wt.-% aromatic amine and 0.023 wt.-% potassium.
[0507] After filtration, the first phase was evaporated in a thin-film evaporator at 200° C. and a pressure of 1 mbar.
[0508] The first phase then contained 99 wt.-% polyol, 0.21 wt.-% DEG, 0.13 wt.-% aromatic amine, 0.025 wt.-% potassium, and an acid value below 0.01 mg KOH / g.
[0509] In the next step, the first phase is mixed with a cation exchange material in the form of a strongly acidic resin material having sulfonic acid groups (here: having the trade name K 2621, which is available from LANXESS Germany GmbH) and an anion exchange material in the form of a weakly basic macroporous anion exchange resin having tertiary amine groups (monofunctional) (available under the trade name MP 62 (available from LANXESS Deutschland GmbH) was contacted. The mixture of the first phase, 9 wt.-% cation exchange material and 9 wt.-% anion exchange material was stirred at 80° C. for 1 hour and filtered using a filter with a pore size of about 70 μm.
[0510] The first phase was then distilled at 200° C. under a pressure of 100 mbar to remove water, resulting in a composition comprising 99 wt.% polyol, 0.12 wt.% DEG, less than 0.006 wt.% aromatic amine and 0.0009 wt.% potassium. The acid number was 0.04 mg KOH / g.
[0511] Example 3A1 shows that cation exchange materials and anion exchange materials can be used simultaneously.
[0512] Example 4A1:
[0513] For Example 4A1, the first phase of Example 4.1 was used as starting material.
[0514] In order to deposit the solid in the first phase, the deposition was carried out for 24 h. In this respect, the first phase was stored in the storage tank for 24 h.
[0515] The supernatant was then filtered using a cascade filter, wherein the first filter had a pore size of 270 μm, the second filter had a pore size of 70 μm, and the third filter had a pore size of 20 μm.
[0516] After filtration, the first phase contained 83 wt.-% polyol, 12.4 wt.-% DEG, 3.1 wt.-% aromatic amine and 0.025 wt.-% potassium.
[0517] After filtration, the first phase was evaporated in a thin-film evaporator at 250° C. and a pressure of 6.5 mbar and subsequently in a short-path evaporator at 250° C. and a pressure of 0.15 mbar.
[0518] The first phase then contained 99 wt.-% polyol, less than 0.1 wt.-% DEG, 0.02 wt.-% aromatic amine and 0.032 wt.-% potassium. The acid value was 0.01 mg KOH / g.
[0519] In a next step, the first phase is contacted with a mixture of 2 wt.-% micronized magnesium silicate (currently micronized magnesium silicate with the trade name Ambosol MP 20, available from PQ France S.A., 60350 Trosly-Breuil, France), 3 wt.-% activated carbon (currently available under the trade name CNSP 1240) and 2 wt.-% water, with stirring, at 110° C. and 10 mbar for 1 h, and then under full vacuum, which is reached at 4 mbar after 3 hours, for a further 3 hours.
[0520] Afterwards, the mixture was filtered using a filter with a pore size of 70 μm to obtain a composition of more than 99 wt.-% polyol, less than 0.1 wt.-% DEG, less than 0.001 wt.-% aromatic amine, less than 0.0003 wt.-% potassium and an acid value of 0.03 mg KOH / g.
[0521] Example 5A1:
[0522] For Example 5A1, the first phase of Example 5 was used as the starting material.
[0523] The first phase was filtered through a filter with a pore size of 90 μm.
[0524] The first phase is then brought into contact with magnesium silicate (currently microparticle magnesium silicate with the trade name Ambosol MP 20, available from PQ France SA, Trosly-Breuil 60350, France) by preparing a mixture of the first phase and 3 wt.-% of magnesium silicate. The mixture is stirred at 100° C. for 2.5 hours.
[0525] Afterwards (without further sedimentation), the first phase was filtered using a filter with a pore size of approximately 3 μm.
[0526] After filtration, the first phase contained 81 wt.-% polyol, 13.1 wt.-% DEG, 5.7 wt.-% aromatic amine and 0.0043 wt.-% potassium.
[0527] After filtration, the first phase was evaporated in a flash evaporator at 190° C. and a pressure of 30 mbar and subsequently in a short-path evaporator at 250° C. and a pressure of 0.15 mbar.
[0528] The first phase then comprises 99 wt.-% polyol, less than 0.1 wt.-% DEG, less than 0.005 wt.-% aromatic amine and 0.0054 wt.-% potassium. The acid value is less than 0.1 mg KOH / g.
[0529] Example 7A1:
[0530] For Example 7A1, the first phase of Example 7 was used as the starting material.
[0531] The first phase was filtered without sedimentation using a filter with a pore size of 20 μm to obtain a composition comprising 59 wt.-% polyol, 19 wt.-% DEG, 8.4 wt.-% aromatic amine, 0.044 wt.-% potassium and 0.4 wt.% water.
[0532] No further post-treatment was carried out, since by now it had become clear that polyurethane materials with SAN contents of up to 15 wt. % could be processed.
[0533] Example 8A1:
[0534] For Example 8A1, the first phase of Example 8 was used as the starting material.
[0535] The first phase was filtered without sedimentation using a filter with a pore size of 20 μm to obtain a composition comprising 79 wt.-% polyol, 16 wt.-% DEG, 3.98 wt.-% aromatic amine, 0.0009 wt.-% potassium and 0.3 wt.% water.
[0536] No further post-processing was performed.
[0537] Example 9A1:
[0538] For Example 9A1, the first phase of Example 9 was used as the starting material.
[0539] The first phase was filtered without sedimentation using a filter with a pore size of 20 μm to obtain a composition comprising 74 wt.-% polyol, 16 wt.-% DEG, 6.7 wt.-% aromatic amine, 0.0067 wt.-% potassium and 0.3 wt.% water.
[0540] No further post-processing was performed.
[0541] Example 10A1:
[0542] For Example 10A1, the first phase of Example 10 was used as the starting material.
[0543] The first phase was filtered without sedimentation using a filter with a pore size of 20 μm to obtain a composition comprising 78.5 wt.-% polyol, 15 wt.-% DEG, 4.83 wt.-% aromatic amine, 0.0165 wt.-% potassium and 0.5 wt.% water.
[0544] No further post-processing was performed.
[0545] Example of workup of the phase rich in amine species, currently the second phase:
[0546] Example 1B1:
[0547] No further workup of the second phase was performed.
[0548] Example 2B1:
[0549] The second phase produced after phase separation was mixed with the distillate of the first phase produced from Example 2A1. This combined phase as a whole is subsequently referred to as the second phase.
[0550] This second phase is distilled in a first distillation consisting of two parts.
[0551] In the first part of the first distillation, DEG was removed by distillation at a bottom temperature of 230° C., a top temperature of 170° C. and a top pressure of 350 mbar.
[0552] Thereafter, a second stage of the first distillation was carried out, in which TDA was distilled.The second stage of the first distillation was carried out using a bottom temperature of 220° C., a top temperature of 130° C. and a top pressure of 4 mbar.
[0553] simulation:
[0554] Example 11:
[0555] A stream consisting of diethylene glycol (DEG), a mixture of toluenediamine (TDA) isomers, water, by-products from the hydrolysis alcoholysis reaction (e.g., potassium hydroxide, potassium carbonate, and potassium bicarbonate), and impurities derived from the polyurethane material 100 (referred to above as the second phase 112) is processed in the following process:
[0556] 1) Filtration to remove solids from the stream (second phase 112);
[0557] 2) performing a first distillation stage 136a in a bottom distillation column to remove DEG and water; and
[0558] 3) performing a second distillation stage 136b to remove residual DEG from the TDA to obtain a crude TDA stream;
[0559] 4) The crude TDA stream comprising 2,4- and 2,6 TDA is then fed to the TDA purification distillation column 140 of the existing TDA plant.
[0560] Use Chemasim TM Simulate (Version 6.6, Fixed Process Simulation Software) and use the following parameters to simulate the above method:
[0561] 15.0 kg / h of solids were removed by filtration at 80° C. from a stream (second phase 112 ) having the following composition:
[0562] m(DEG)=52.5kg / h
[0563] m(2,4-TDA)=24.0kg / h
[0564] m(2,6-TDA)=6.0kg / h
[0565] m(H2O)=2.5kg / h
[0566] m(solid)=15.0kg / h
[0567] At the evaporator stage, the liquid filtrate (m = 85.0 kg / h) was fed to the first distillation stage 136a (distillation column, p = 100 mbar, reflux ratio = 4 g / g, theoretical number of stages: 18). 71 kW of energy was supplied to the evaporator, so that the bottom temperature reached 198.5 ° C. The energy supplied brought the liquid to boiling. A top stream with T gas = 78 ° C was formed, which had the following composition:
[0568] w(DEG)=0.952g / g
[0569] w(2,4-TDA=219ppb
[0570] w(2,6-TDA)=32ppb
[0571] w(H2O)=0.048g / g
[0572] And with T 液体 = 198.5°C bottom stream, the bottom stream having the following composition:
[0573] w(DEG)=0.077g / g
[0574] w(2,4-TDA=0.738g / g
[0575] w(2,6-TDA)=0.185g / g
[0576] w(H2O)=23ppm
[0578] The top stream is condensed and recycled as liquid to the reaction section. The bottom stream is transferred to the second distillation stage 136b (distillation column, p = 70 mbar, reflux ratio = 4 g / g, theoretical number of stages: 20) for further purification. A filter integrated into the external circulation loop of the evaporator stage is used to remove solids that may have precipitated in the distillation column bottom during the removal of DEG and water.
[0579] The bottom stream is fed to the second distillation stage 136b at the level of theoretical stage 10. 4.1 kW of energy is supplied to the evaporator in the bottom of the column, causing the liquid to boil. 气体 = 170.6°C top stream having the following composition:
[0580] w(DEG)=0.484g / g
[0581] w(2,4-TDA=0.430g / g
[0582] w(2,6-TDA)=0.086g / g
[0583] w(H2O)=148ppm
[0584] And with T 液体 =194.2°C bottom stream, the bottom stream having the following composition:
[0585] w(DEG)=300ppm
[0586] w(2,4-TDA=0.797g / g
[0587] w(2,6-TDA)=0.203g / g
[0588] w(H2O)=0g / g
[0590] The resulting crude TDA stream can be further purified in a third distillation 136c (third distillation column) to remove trace amounts of DEG. This third distillation stage 136c can be a stand-alone TDA distillation (which purifies TDA by removing TDA isomers as a side stream, trace amounts of DEG as an overhead stream, and impurities with higher boiling points than TDA isomers as TDA TAR), or an existing TDA purification column 140 in an existing TDA production facility.
[0591] Example 12:
[0592] A stream (second phase 112) consisting of diethylene glycol (DEG), a mixture of TDA isomers, water, by-products from the hydrolysis alcoholysis reaction (e.g., potassium hydroxide, potassium carbonate, and potassium bicarbonate), and impurities originating from the polyurethane material 100 is processed in the following process:
[0593] 1) Filtration to remove solids from the stream (second phase 112);
[0594] 2) performing TDA extraction and recovery of the solvent used for the extraction (extraction solvent in the form of, for example, toluene, xylene, diisopropyl ether), comprising extracting TDA with the aid of an extraction solvent, recovering the extraction solvent and purifying the TDA stream in a first distillation stage 136a;
[0595] 3) distilling the TDA stream in a second distillation stage 136b to remove residual DEG, yielding a TDA stream (also referred to as crude TDA) comprising different TDA isomers (2,4- and 2,6-TDA); and
[0596] 4) Purification of the crude TDA in a third distillation stage 136c to purify the TDA. This third distillation stage 136c can be done in a dedicated distillation stage or in an already existing distillation as part of an existing TDA production plant.
[0597] Use Chemasim TM Simulate (Version 6.6, Fixed Process Simulation Software) and use the following parameters to simulate the above method:
[0598] 15.0 kg / h of solids were removed by filtration at 80° C. from a stream (second phase 112 ) having the following composition:
[0599] m(DEG)=52.5kg / h
[0600] m(2,4-TDA)=24.0kg / h
[0601] m(2,6-TDA)=6.0kg / h
[0602] m(H2O)=2.5kg / h
[0603] m(solid)=15.0kg / h
[0604] A liquid filtrate is obtained. Water is added to the liquid filtrate (m=85.0 kg / h) to improve the extraction with the non-polar extraction solvent. In a specific example, 30 kg / h of water are added to obtain a mixture with the following composition:
[0605] w(DEG)=0.457g / g
[0606] w(2,4-TDA)=0.209g / g
[0607] w(2,6-TDA)=0.052g / g
[0608] w(H2O)=0.283g / g.
[0609] In an extraction column operated in countercurrent mode (T=50° C., p=1 bar, stages: 10), 200 kg / h of toluene were used to obtain an extract stream having the following composition:
[0610] w(DEG)=0.010g / g
[0611] w(2,4-TDA)=0.103g / g
[0612] w(2,6-TDA)=0.024g / g
[0613] w(H2O)=0.003g / g
[0614] w(toluene)=0.860g / g
[0615] and a raffinate stream having the following composition:
[0616] w(DEG)=0.603g / g
[0617] w(2,4-TDA)=5.9*10 -7 g / g
[0618] w(2,6-TDA)=0.006g / g
[0619] w(H2O)=0.384g / g
[0620] w(toluene)=0.007 g / g.
[0621] The extract stream is purified in the subsequent first distillation stage 136a. The distillation is carried out at 0.2 bar, a top temperature of 49°C, and a bottom temperature of 225.6°C. A reflux ratio of 0.5 g / g is used. The column has 20 theoretical stages. A bottom stream containing:
[0622] w(DEG)=3.4*10 -5 g / g
[0623] w(2,4-TDA)=0.814g / g
[0624] w(2,6-TDA)=0.186g / g
[0625] w(H2O)=0g / g
[0626] w(toluene)=0g / g
[0628] This stream can be further purified in a TDA purification column as described in the prior art using an overhead distillation column or a side-flow distillation column to remove high-boiling impurities such as TDA TAR. This TDA distillation column (also referred to as the third distillation stage 136c) can be a dedicated distillation column or a distillation column 140 integrated into an existing TDA production facility.
[0629] The top stream of the first distillation stage 136a is transferred to a phase separator consisting of:
[0630] w(DEG)=0.012g / g
[0631] w(2,4-TDA)=4.2*10-8g / g
[0632] w(2,6-TDA)=5.5*10-9g / g
[0633] w(H2O)=0.003g / g
[0634] w(toluene)=0.985g / g
[0635] A DEG-rich layer and a toluene-rich layer are formed in the phase separator. The DEG-rich layer having the following is recycled to the reaction section:
[0636] w(DEG)=0.708g / g
[0637] w(2,4-TDA)=33ppb
[0638] w(2,6-TDA)=11ppb
[0639] w(H2O)=0.280g / g
[0640] w(toluene)=0.012g / g
[0641] The toluene-rich layer having the following contents was reused in the (TDA) extraction column:
[0642] w(DEG)=0.006g / g
[0643] w(2,4-TDA)=42ppb
[0644] w(2,6-TDA)=5ppb
[0645] w(H2O)=0.001g / g
[0646] w(toluene)=0.993g / g
[0648] The raffinate stream of the extraction column is transferred to a distillation column where DEG and water are distilled off as overhead streams and the solid impurities of the stream (second phase 112) are purged. The overhead stream is transferred to a phase separation step after condensation to separate a toluene-rich layer and a DEG-rich layer. From there it is recycled back to the solvolysis reaction.
[0649] Example 13:
[0650] The second phase 112 obtained from the hydrolysis alcoholysis of the polyurethane material 100 was distilled in a laboratory scale distillation setup consisting of a distillation column as described in Table 1 .
[0651] Table 1: Design and operating conditions of a laboratory-scale distillation column:
[0652] filler BX (analog) Filling height 140cm Theoretical level 20 Top pressure >2 mbar Δp 2 mbar to 15 mbar outer diameter 9cm / 5cm Tower Height 150cm Tower materials Glass evaporator Natural Cycle Condenser Glass (oil as cooling medium)
[0653] The flow (second phase 112) consists of:
[0654] m(DEG)=1396.4g
[0655] m(TDA)=207.5g
[0656] m(MDA)=10.1g
[0657] m(salt)=51.3g
[0658] m(H2O)=9.7g
[0659] m(unknown)=243.1g
[0660] The tower used was operated in batch mode. 20 to 100 g fractions were taken out from the top of the tower and analyzed using HPLC. Detailed information on the take-out amounts and corresponding operating conditions is summarized in Table 2.
[0661] Table 2: Overview of fractions and operating conditions of the distillation column
[0662]
[0663]
[0664] Fractions 1 to 17 are pure DEG. Starting from fraction 18, TDA can be withdrawn from the top of the column. As the bottom temperature (and distillation time, respectively) increases, the TDA content of the fraction withdrawn from the top of the column increases. TDA predominates in fraction 20 (fraction 20 contains 52 wt.-% TDA). Following a mixed fraction (fraction 22) containing a small amount of DEG, a TDA fraction can be obtained.
Claims
1. A method for recovering a polyol substance (118) from a polyurethane material (100), preferably an end-of-life (eol) polyurethane material, wherein the method comprises the following: - alcoholizing the polyurethane material (100) by contacting the polyurethane material (100) with an alcoholizing substance (102), wherein during alcoholization of the polyurethane material (100), a mixture (108) containing a polyol substance (118) and an amine substance (122) is formed; - allowing the mixture (108) to settle, wherein a phase rich in polyol substances, in particular a first phase (110) and a phase rich in alcoholized substances, in particular a second phase (112) are formed; - post-treating (116) the phase rich in polyol substance, in particular the first phase (110), by purifying the polyol substance (118), wherein the purification comprises two or more of the following: - evaporating the phase in one or more evaporators (126, 128); - contacting the phase with an ion exchange material (130, 132); - contacting the phase with one or more adsorbents (134); After the post-treatment (116), the phase rich in polyol substances, in particular the first phase (110), has an acid value of 0.1 mgKOH / g or less.
2. The method according to claim 1, wherein: Prior to the purification, the phase rich in polyol substances, in particular the first phase (110), is purified by solid-liquid separation, by which solids are removed, wherein the solid-liquid separation comprises or consists of one or more of the following: filtration, centrifugation, decantation, extraction.
3. The method according to claim 1 or 2, wherein: Before or after allowing the mixture (108) to settle, solids are removed from the mixture (108), preferably by one or more of: filtration, centrifugation, decantation.
4. The method according to any one of claims 1 to 3, wherein: During allowing the mixture (108) to settle, phase separation of the mixture (108) into the first phase (110) and the second phase (112) occurs, and wherein, after the post-treatment (116), the first phase (110) has a potassium content of about 0.1 wt.-% or less, in particular about 0.01 wt.-% or less, for example about 0.005 wt.-% or less, based on the total weight of the phase (110).
5. The method according to any one of claims 1 to 4, wherein: For the alcoholization of the polyurethane material (100), about 0.2 parts by weight or more and / or about 5 parts by weight or less of the alcoholizing substance (102) is used per part by weight of the polyurethane material (100), preferably about 0.4 parts by weight or more and / or about 2 parts by weight or less of the alcoholizing substance (102) per part by weight of the polyurethane material (100), in particular about 0.6 parts by weight or more and / or about 1.5 parts by weight or less of the alcoholizing substance (102) per part by weight of the polyurethane material (100), for example about 0.8 parts by weight or more and / or about 1.2 parts by weight or less of the alcoholizing substance (102) per part by weight of the polyurethane material (100).
6. The method according to any one of claims 1 to 5, wherein: The one or more evaporators (126, 128) are selected from one or more of the following, for example two or more: a thin film evaporator (126), a short path evaporator (128), a falling film evaporator, a rotary evaporator.
7. The method according to any one of claims 1 to 6, wherein: The amount of water (106) added during or before the alcoholization step is such that the water content of the resulting mixture (108) is from about 0.2 eq. to about 30 eq. based on the amount of breakable bonds of the polyurethane material (100).
8. The method according to any one of claims 1 to 7, wherein: The mixture (108) is contacted with one or more adsorbents (134) before being allowed to settle, wherein preferably the one or more adsorbents (134) are selected from the group consisting of: activated carbon, silicon dioxide, silicates, in particular alkali metal silicates and / or for example magnesium silicate, or a mixture of two or more thereof.
9. The method according to any one of claims 1 to 8, wherein: The post-treatment (116) of the phase rich in polyol substances, in particular the first phase (110), comprises contacting the phase rich in polyol substances, in particular the first phase (110), with a cation exchange material (130) or an anion exchange material (132) or a mixture thereof, or contacting the phase with a cation exchange material (130) and an anion exchange material (132) in sequence.
10. The method according to any one of claims 1 to 9, wherein: The one or more adsorbents (134) are activated carbon, silicon dioxide, silicates, in particular alkali metal silicates and / or alkaline earth metal silicates, such as magnesium silicate, or mixtures of two or more thereof.
11. The method according to any one of claims 1 to 10, wherein: During the time the mixture (108) is allowed to settle, phase separation of the mixture (108) into the first phase (110) and the second phase (112) occurs, and wherein, after the post-treatment (116), the first phase (110) has an aromatic amine content of about 0.03 wt.-% or less, preferably about 0.01 wt.-% or less, based on the total weight of the first phase (110) after the post-treatment (116).
12. The method according to any one of claims 1 to 11, wherein: During and after the water addition, the internal temperature of the mixture (108) is maintained at about 150°C to about 240°C, preferably about 170°C to about 220°C, and at a pressure of about 1 bar to about 60 bar.
13. The method according to any one of claims 1 to 12, wherein: One or more of the one or more evaporators (126, 128) is a thin film evaporator (126) that operates at about 180°C to about 270°C and / or at a pressure of about 0.1 mbar to about 10 mbar.
14. The method according to any one of claims 1 to 13, wherein: The polyurethane material (100) is a polyurethane foam, a polyurethane elastomer, a polyurethane adhesive, a polyurethane coating or a mixture thereof, wherein the polyurethane material (100) has a styrene acrylonitrile copolymer content of up to 15 wt.-%, based on the total weight of the polyurethane material (100).
15. A method for preparing a polyurethane material (100) by reacting a polyol substance (118) obtained by the method according to claims 1 to 14 with an isocyanate substance.
Citation Information
Patent Citations
Method for the distillative recovery of toluylenediamine
EP1706370A1
Process for the production of toluylene diamine
EP1746083A1
Process for the production of the toluene diisocyanate
EP1864969A1
Method for recovering raw materials from polyurethane products
WO2020260387A1
Improved method of recycling polyurethane materials
WO2021023889A1